Glasses and glass ceramics including metal oxide concentration gradient

JP2025022984AInactive Publication Date: 2025-02-14CORNING INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024205330
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2015-07-21
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0023】 先の一般的な説明および以下の詳細な説明の両方とも、単に説明のためであり、請求項の性質および特徴を理解するための概要または骨子を提供することが意図されているのが理解されよう。添付図面は、さらなる理解を与えるために含まれ、本明細書に包含され、その一部を構成する。図面は、1つ以上を実施の形態を図解しており、説明と共に、様々な実施の形態の原理および作動を説明する働きをする。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022984000001_ABST
    Figure 2025022984000001_ABST
Patent Text Reader

Abstract

To provide thin glass-based articles that exhibit improved fracture resistance.SOLUTION: The glass-based article has a first surface and a second surface opposing the first surface that define a thickness of about 3 millimeters or less, and has a stress profile where all points of the stress profile in a thickness range from about 0 t to 0.3 t and from more than 0.7 t has a tangent that is less than about -0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer. In some embodiments, the glass-based article has a non-zero metal oxide concentration that varies along at least a portion of the thickness (e.g., 0 t to about 0.3 t).SELECTED DRAWING: Figure 39
Need to check novelty before this filing date? Find Prior Art

Description

Description of Related Applications

[0001] This application claims the benefit of priority under Title 35, Section 119 of U.S. Provisional Patent Application No. 62 / 194967, filed July 21, 2015, U.S. Provisional Patent Application No. 62 / 171110, filed June 4, 2015, U.S. Provisional Patent Application No. 62 / 117585, filed February 18, 2015, and U.S. Provisional Patent Application No. 62 / 061372, filed October 8, 2014, the contents of which are relied upon and are incorporated herein by reference in their entirety. This application is also a divisional application of Japanese Patent Application No. 2022-181682, filed November 14, 2022. [Technical field]

[0002] The present disclosure relates to glass-based articles that exhibit improved damage resistance, including improved fracture resistance, and more particularly to glass and glass-ceramic articles that exhibit a non-zero metal oxide concentration gradient or a metal oxide concentration that varies along a substantial portion of their thickness. [Background technology]

[0003] Glass-based articles often experience severe impacts that can result in large scratches on the surface of such articles. Such scratches can extend to a depth of up to about 200 micrometers from the surface. Traditionally, thermally strengthened glass has been used to prevent breakage that may result in such scratches in glass. Because thermally strengthened glass often exhibits a large compressive stress (CS) layer (e.g., about 21% of the total thickness of the glass), which can prevent the propagation of scratches and therefore breakage. An example of a stress profile resulting from thermal strengthening is shown in FIG. 1. In FIG. 1, a heat-treated glass-based article 100 has a first surface 101, a thickness t1, and a surface CS 110. The glass-based article 100 exhibits a CS that decreases from the first surface 101 to a depth of layer (DOL) 130 as defined herein, where the stress changes from compressive to tensile stress and reaches a maximum central tension (CT) 120.

[0004] Thermal strengthening is currently limited to thick glass-based articles (i.e., glass-based articles having a thickness t1 of about 3 millimeters or more) because a sufficient temperature gradient must be created between the core and surface of such articles to achieve thermal strengthening and the desired residual stresses. Such thick articles are undesirable or impractical in many applications, such as displays (e.g., consumer electronics including mobile phones, tablets, computers, navigation systems, etc.), buildings (e.g., windows, shower panels, countertops, etc.), transportation (e.g., automobiles, trains, aircraft, marine vessels, etc.), appliances, or any application requiring good fracture resistance but a thin, lightweight article.

[0005] Known chemically strengthened glass-based articles do not exhibit the stress profile of thermally strengthened glass-based articles, but chemical strengthening is not limited by the thickness of the glass-based article in the same manner as thermal strengthening. An example of a stress profile resulting from chemical strengthening (e.g., by ion exchange) is shown in FIG. 2. In FIG. 2, a chemically strengthened glass-based article 200 has a first surface 201, a thickness t2, and a surface CS 210. The glass-based article 200 exhibits a CS that decreases from the first surface 201 to a DOC 230 as defined herein, at the depth of this layer, the stress changes from compressive to tensile stress and reaches a maximum CT 220. As shown in FIG. 2, such a profile exhibits a flat CT region, or a CT region with constant or nearly constant tensile stress, and a maximum CT value that is often smaller than the maximum median value shown in FIG. 1. Summary of the Invention [Problem to be solved by the invention]

[0006] Thus, there is a need for thin glass-based articles that exhibit improved fracture resistance. [Means for solving the problem]

[0007] A first aspect of the present disclosure relates to a glass-based article having a first surface and a second surface opposite the first surface that defines a thickness (t) (e.g., about 3 millimeters or less, about 1 millimeter or less, or about 0.5 millimeters or less), and a stress profile extending along the thickness. In one or more embodiments, all points of the stress profile between a thickness range of about 0·t to 0.3·t and greater than 0.7·t have a tangent less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer.

[0008] In embodiments, the glass-based article has a non-zero metal oxide concentration that varies along a substantial portion or the entire thickness of the glass-based article. The variation in metal oxide concentration may be referred to herein as a gradient. In some embodiments, the concentration of the metal oxide varies non-zero along a thickness range of about 0·t to 0.3·t. In some embodiments, the concentration of the metal oxide varies non-zero along a thickness range of about 0·t to 0.35·t, about 0·t to 0.4·t, about 0·t to 0.45·t, or about 0·t to 0.48·t. The metal oxide may be described as causing stress in the glass-based article. The variation in metal oxide concentration may include a change of about 0.2 mol % along a thickness segment of about 100 micrometers. The variation in concentration may be continuous along the thickness range. In some embodiments, the variation in concentration may be continuous along a thickness segment ranging from about 10 micrometers to about 30 micrometers.

[0009] In some embodiments, the concentration of metal oxide decreases from the first surface to a point between the first surface and the second surface, and then increases from that point to the second surface.

[0010] As used herein, the metal oxide includes strengthening ions or ions that cause CS in the glass-based article. In some embodiments, the metal oxide has the largest ionic diameter of all of the metal oxides in the glass-based substrate. In one or more embodiments, the metal oxide may include an alkali metal oxide or a combination of different metal oxides or alkali metal oxides. Exemplary metal oxides include Ag2O. Exemplary alkali metal oxides include any one or more of Li2O, Na2O, K2O, Rb2O, and Cs2O. The metal oxide may be present in a non-zero concentration of the particular metal oxide that varies along a substantial portion or the entire thickness of the glass-based article. In some embodiments, the concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface, and increases from that point to the second surface. The concentration of the metal oxide may be non-zero at that point.

[0011] The concentration of the metal oxide may be about 0.05 mol% or more or about 1 mol% or more through the thickness. For example, the concentration of Na2O may be about 0.05 mol% or more through the thickness of the glass-based article, but such concentration of Na2O decreases from the first surface to a point between the first surface and the second surface, and increases from that point to the second surface. In some cases, the total concentration of the metal oxide along the entire thickness of the glass-based article is in the range of about 1 mol% to about 20 mol%. In some embodiments, the concentration of the metal oxide near the surface may be greater than 1 or 1.5 times (e.g., 5 times, 10 times, 15 times, or even 20 times) the concentration of the same metal oxide at a depth in the range of about 0.4·t to about 0.6·t. The concentration of the metal oxide may be determined from a baseline amount of the metal oxide concentration in the glass-based article before it is altered to exhibit a concentration profile (i.e., a gradient or variation as described herein).

[0012] In one or more embodiments, the glass-based article has a concentration of a first metal oxide and a concentration of a second metal oxide such that the concentration of the first metal oxide ranges from about 0 mol% to about 15 mol% along a first thickness range of about 0t to about 0.5t and the concentration of the second metal oxide ranges from about 0 mol% to about 10 mol% along a second thickness range of about 0 micrometers to about 25 micrometers. The glass-based article may have a concentration of an optional third metal oxide. The first metal oxide may be Na2O and the second metal oxide may be KO.

[0013] In one or more embodiments, the glass-based article has a surface CS of about 150 MPa or greater, or about 200 MPa or greater. In one or more embodiments, the glass-based article may have a surface CS of greater than about 300 MPa, greater than about 600 MPa, or greater than about 700 MPa. The glass-based article may exhibit a chemical depth of about 0.4·t or greater.

[0014] In some embodiments, the glass-based article may have a CS layer extending from the first surface to a DOC of about 0.1·t or greater. In some cases, the glass-based article may have a layer of CT having a non-zero metal oxide concentration that varies along a substantial portion of the thickness, t. The CT layer may exhibit a maximum CT such that the ratio of maximum CT to surface CS is in the range of about 0.01 to about 0.5. The maximum CT may be about 25 MPa or greater.

[0015] In one or more embodiments, the glass-based article has a thickness that is less than 1 square inch when the glass-based article is broken. 2 In some cases, the glass-based article may exhibit a fracture resistance of at least 2 fragments per square inch. 2 ) may break into 3 or more pieces, 5 or more pieces, or 10 or more pieces.

[0016] In some cases, the glass-based article has a thermal conductivity of about 0 J / m2 Over 20J / m 2 It may exhibit a stored tensile energy of less than 100 kPa.

[0017] The CT region of one or more embodiments of the glass-based article has the formula: Stress(x)=MaxCT-(((MaxCT·(n+1)) / 0.5 n )·|(x / t)-0.5| n ) where MaxCT is the maximum CT value given as a positive value in units of MPa, x is the position along the thickness (t) in micrometers, and n is between 1.5 and 5 (or 1.8 to about 2).

[0018] The glass-based article may include an amorphous structure, a crystalline structure, or a combination thereof. The glass-based article may be transparent or opaque. In some embodiments, the glass-based article exhibits a substantially white or substantially black color. Additionally or alternatively, the glass-based article may include a colorant that imparts a particular color.

[0019] A second aspect of the disclosure relates to an amorphous glass substrate having a composition including, in mole percent, SiO in an amount ranging from about 68 to about 75, AlO in an amount ranging from about 12 to about 15, BO in an amount ranging from about 0.5 to about 5, LiO in an amount ranging from about 2 to about 8, NaO in an amount ranging from about 0 to about 6, MgO in an amount ranging from about 1 to about 4, ZnO in an amount ranging from about 0 to about 3, and CaO in an amount ranging from about 0 to about 5. In some embodiments, the glass substrate has a ratio of LiO to RO ranging from about 0.5 to about 1; a difference between the total amount of RO and the amount of AlO ranging from about -5 to about 0; and R in an amount ranging from about 0 to about 3. x the difference between the total amount of O (mol %) and the amount of Al2O3; and the ratio of the amount of MgO (mol %) to the total amount of RO (mol %) ranging from about 0 to about 2.

[0020] In one or more embodiments, the glass substrate is ion-exchangeable, while in other embodiments, the glass substrate is strengthened by an ion-exchange process.

[0021] A third aspect of this disclosure relates to a method of forming a fracture resistant glass-based article as described herein, an embodiment of the method comprising providing a glass-based substrate having a first surface and a second surface defining a thickness of about 3 millimeters or less, and generating a stress profile in the glass-based substrate having a CT layer and a CS layer, the CS layer having a surface CS, a chemical depth of about 0.4t or greater and a DOC of about 0.1·t or greater, the CT layer having a maximum CT, and a ratio of the maximum CT to the surface CS of about 0.01 to about 0.5.

[0022] Additional features and advantages are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments as described herein, including the following detailed description, the claims, and the accompanying drawings.

[0023] It is to be understood that both the foregoing general description and the following detailed description are merely explanatory and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiments, and together with the description, serve to explain the principles and operation of the various embodiments. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a cross-sectional view through the thickness of a known thermally strengthened glass-based article. [Diagram 2] FIG. 1 is a cross-sectional view through the thickness of a known chemically strengthened glass-based article. [Diagram 3] FIG. 1 is a cross-sectional view through the thickness of a chemically strengthened glass-based article according to one or more embodiments of the present disclosure. [Figure 4]Schematic cross-section of a ring-on-ring device [Diagram 5] FIG. 1 is a graph showing the concentration of Na2O in known chemically strengthened glass-based articles and in glass-based articles according to one or more embodiments of the present disclosure. [Figure 6] Graph showing CT and DOC values ​​as a function of ion exchange time, according to one or more embodiments of the present disclosure. [Figure 7] Graph comparing stress profiles as a function of depth for known chemically strengthened glass-based articles and glass-based articles according to one or more embodiments of the present disclosure. [Figure 8] Graph of stress profiles for known chemically strengthened glasses and glass-ceramics [Figure 9] Graphs of stress profiles for glasses and glass-ceramics according to one or more embodiments of the present disclosure. [Figure 9A] Graph of breakage height in drop test of Example 3D [Figure 10] Graph comparing known stress profiles of chemically strengthened glass-based articles and the stress profile of a glass-based article according to one or more embodiments of the present disclosure. [Figure 11] Graph showing stress profiles for Examples 4A-4D as a function of thickness [Figure 12] Graph showing individual stored tensile energy data points for Examples 4B-4D [Figure 13] Graph showing K2O and Na2O concentration as a function of depth for Examples 4B-4D [Figure 14] Graph showing the same data as in Figure 13, but with a different scale to more clearly show the concentration of Na2O as a function of depth. [Figure 15] Graph showing stress profiles for Examples 4A and 4C-4F as a function of depth [Figure 16] Graph showing different scales in Figure 14 [Figure 17] Graph showing stress profiles for Examples 5A-5G as a function of depth [Figure 18]Graph showing DOC values ​​for Examples 5A-5G as a function of duration of the second and / or third ion exchange steps. [Figure 19] Graph showing CT values ​​of Examples 5A-5G as a function of duration of the second and / or third ion exchange steps. [Figure 20] Graph showing stress profiles of Examples 6A-1 to 6A-6 as a function of depth [Figure 21] Graph showing CT and DOC values ​​of Examples 6A-1 to 6A-6 as a function of ion exchange time [Figure 22] Graph showing stress profiles of Examples 6B-1 through 6B-6 as a function of depth. [Figure 23] Graph showing CT and DOC values ​​of Examples 6B-1 to 6B-6 as a function of ion exchange time [Figure 24] Graph showing stress profiles of Examples 6C-1 through 6C-6 as a function of depth. [Diagram 25] Graph showing CT and DOC values ​​of Examples 6C-1 to 6C-6 as a function of ion exchange time [Figure 26] Graph showing stress profiles for Examples 6D-1 to 6D-6 as a function of depth [Figure 27] Graph showing CT and DOC values ​​of Examples 6D-1 to 6D-6 as a function of ion exchange time [Figure 28] Graph showing CT as a function of ion exchange time for Examples 7A-7G [Figure 29] Graphs showing the change in median tension value and stored tensile energy as a function of ion exchange time, both for Examples 7A-7G. [Diagram 30] Graph showing stress profiles for Comparative Example 8A and Example 8B as a function of depth [Diagram 31] Graph showing stored tensile energy as a function of CT for Comparative Example 8A and Example 8B [Diagram 32] Graph showing stored tensile energy as a function of CT for Comparative Example 8C and Example 8D [Diagram 33] Graph showing drop breakage height for Examples 2, 6 and 9B, and Comparative Example 9A [Diagram 34] Graph showing ring-on-ring results during polishing for Examples 2, 6, and 9B, and Comparative Example 9B [Diagram 35] Weibull distribution plot showing 4-point bend results for Examples 2 and 9B [Diagram 36] FIG. 1 is a schematic cross-sectional view of an embodiment of an apparatus used to perform the inverted ball on sandpaper (IBoS) test described in this disclosure. [Figure 37] FIG. 1 is a schematic cross-sectional view showing the dominant failure mechanism due to the introduction of damage in bending that typically occurs in glass-based articles used in portable or handheld electronic devices. [Figure 38] 1 is a flow diagram of a method for performing IBoS testing on the apparatus described herein; [Figure 39] Graphs illustrating various stress profiles according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Reference will now be made in detail to various embodiments, examples of which are illustrated in the accompanying examples and drawings.

[0026] In the following description, like reference characters refer to like or corresponding parts throughout the several figures shown in the drawings. It is also understood that, unless otherwise specified, terms such as "upper", "lower", "outer", "inner" and the like are words of convenience and should not be considered limiting terms. Moreover, whenever a group is described as comprising at least one of a group of elements or combinations thereof, it is understood that the group may comprise, consist essentially of, or consist of any of those elements listed, either individually or in combination with each other. Similarly, whenever a group is described as consisting of at least one of a group of elements or combinations thereof, it is understood that the group may consist of any of those elements listed, either individually or in combination with each other. Unless otherwise specified, ranges of values, when recited, include both the upper and lower limits of the range, as well as any ranges therebetween. As used herein, unless otherwise specified, nouns are intended to refer to "at least one" or "one or more" objects. It is also to be understood that the various features disclosed in this specification and in the drawings can be used in any and all combinations.

[0027] As used herein, the terms "glass-based article" and "glass-based substrate" are used in the broadest sense to include any object made entirely or partially from glass. Glass-based articles include laminates of glass and non-glass materials, laminates of glass and crystalline materials, and glass-ceramics (containing amorphous and crystalline phases). Unless otherwise specified, all compositions are expressed in mole percent (mol%).

[0028] Please note that the terms "substantially" and "about" may be used herein to represent the inherent degree of uncertainty that may contribute to any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent the degree to which a quantitative representation may vary from the stated standard without changing the basic functionality of the subject matter at issue. Thus, for example, a glass-based article that is "substantially free of MgO" is one in which MgO is not actively added or batched into the glass-based article, but may be present in negligible amounts as a contaminant.

[0029] With reference to the drawings generally, and Figures 1-3 in particular, it will be understood that the illustrations are for purposes of describing particular embodiments, and are not intended to limit the scope of the disclosure or the appended claims thereto. The drawings are not necessarily drawn to scale, and certain features and particular views of the drawings may be shown exaggerated in scale or schematic for clarity and conciseness.

[0030] As used herein, DOC refers to the depth within a glass-based article where stress changes from compressive to tensile. At the DOC, the stress crosses from positive (compressive) to negative (tensile) stress (e.g., 130 in FIG. 1 ), and therefore exhibits a stress value of zero.

[0031] As used herein, the terms "chemical depth," "chemical depth of layer," and "depth of chemical layer" may be used interchangeably and refer to the depth to which metal oxide or alkali metal oxide ions (e.g., metal ions or alkali metal ions) diffuse into a glass-based article and the depth at which the concentration of the ions reaches a minimum value as determined by electron probe microanalysis (EPMA) or glow discharge optical emission spectroscopy (GD-OES). In particular, the depth of NaO diffusion or the depth of Na + Ion concentrations may be determined using EPMA and FSM (described in more detail below).

[0032] According to convention commonly used in the art, compression is expressed as a negative (<0) stress and tension is expressed as a positive (>0) stress, however, throughout this description, CS will be expressed as a positive or absolute value - i.e., as set forth herein, CS = |CS|.

[0033] Described herein are thin, chemically strengthened glass-based articles, including glasses such as silicate glasses, including alkali-containing glasses, and glass ceramics, that may be used as cover glasses for portable electronic devices and touch-enabled displays. The glass-based articles may also be used in displays (or display articles) (e.g., billboards, point-of-sale systems, computers, navigation systems, etc.), architectural articles (walls, fixtures, panels, windows, etc.), transportation articles (e.g., automotive applications, trains, aircraft, marine vessels, etc.), appliances (e.g., washing machines, dryers, dishwashers, refrigerators, etc.), or any article requiring some degree of fracture resistance.

[0034] In particular, the glass-based articles described herein are thin and typically exhibit stress profiles that can only be achieved by thermally strengthening thicker glass articles (e.g., greater than about 2 or 3 mm in thickness). The glass-based articles exhibit unique stress profiles along their thickness. In some cases, the glass-based articles exhibit surface CS greater than thermally strengthened glass articles. In one or more embodiments, the glass-based articles exhibit a greater depth of compression layer (CS increases or decreases more gradually than known chemically strengthened glass-based articles) such that the glass-based articles exhibit significantly improved fracture resistance even when the glass-based article or a device containing it is dropped onto a hard rough surface. The glass-based articles of one or more embodiments exhibit a greater maximum CT value than some known chemically strengthened glass substrates.

[0035] CS and depth of compressive stress layer ("DOL") are measured using means known in the art. DOL is distinguished from DOC by a measurement technique in which DOL is determined by a surface stress meter (FSM) using a commercially available instrument such as the FSM-6000 manufactured by Luceo Co., Ltd. (Tokyo, Japan), and methods for measuring CS and depth of layer are described in ASTM 1422C-99, entitled "Standard Specification for Chemically Strengthened Flat Glass," and ASTM 1279.19779, entitled "Standard Test Method for Non-Destructive Photoelastic Measurement of Edge and Surface Stresses in Annealed, Heat-Strengthened, and Fully-Tempered Flat Glass," the contents of which are incorporated herein by reference in their entirety. Surface stress measurement relies on accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is then measured by methods known in the art, such as the fiber and four-point bend methods, and the bulk cylinder method, both of which are described in ASTM standard C770-98 (2008), entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein by reference in their entireties.

[0036] For reinforced glass-based articles where the CS layer extends to greater depths within the glass-based article, the FSM technique may suffer from contrast issues that affect the observed DOL values. At deeper DOL values, the contrast between the TE and TM spectra will be inadequate and therefore the calculation of the difference between the TE and TM spectra - the determination of the DOL - will be more difficult. Furthermore, the FSM technique cannot determine the stress profile (i.e. the variation of CS as a function of depth within the glass-based article). Moreover, the FSM technique cannot determine the DOL resulting from the ion exchange of certain elements, such as, for example, sodium with lithium.

[0037] In order to more accurately determine the DOC and stress profiles for reinforced glass-based articles, the techniques described below were developed.

[0038] In U.S. Patent Application No. 13 / 463,322, filed May 3, 2012 by Rostislav V. Roussev et al., which claims priority to U.S. Provisional Patent Application No. 61 / 489,800, filed May 25, 2011, entitled "Systems And Methods for Measuring the Stress Profile of Ion-Exchanged Glass" (hereinafter "Roussev I"), two methods are disclosed to obtain detailed and accurate stress profiles (stress as a function of depth) of tempered or chemically strengthened glass. Spectra of combined optical modes for TM and TE polarizations are collected by a prism coupling technique and used in total to obtain detailed and accurate TM and TE refractive index profiles n TM (z) and n TE (z). The contents of the prior application are hereby incorporated by reference in their entirety.

[0039] In one embodiment, the inverse Wenzel-Kramers-Brillouin (IWKB) method is used to obtain a detailed refractive index profile from the mode spectrum.

[0040] In another embodiment, the detailed index profile is obtained by fitting the measured mode spectrum to a numerically calculated spectrum of a predetermined functional form that describes the shape of the index profile, and obtaining the parameters of the functional form from the best fit. The detailed stress profile S(z) is calculated from the difference between the obtained TM and TE index profiles by using known values ​​of the stress optical coefficient (SOC): S(z) = [n TM (z)-n TE (z)] / SOC (2) For small values ​​of SOC, the birefringence n TM (z)-n TE (z) is the refractive index n TM (z) and n TE (z) is a small percentage (typically on the order of 1%) of the modal effective refractive index. To obtain a stress profile that is not significantly distorted by noise in the measured modal spectrum, it is necessary to determine the modal effective refractive index with an accuracy on the order of 0.00001 RIU. The method disclosed in Roussev I further includes techniques applied to the raw data to ensure such high accuracy of the measured modal refractive index despite noise and / or poor contrast in the collected TE and TM mode spectra or images of the mode spectra. Such techniques include noise averaging, filtering, and curve fitting to find the locations of extrema corresponding to the modes with sub-pixel resolution.

[0041] Similarly, U.S. Patent Application No. 14 / 033,954, filed September 23, 2013 by Rostislav V. Roussev et al., which claims priority to U.S. Provisional Patent Application No. 61 / 706,891, filed September 28, 2012, entitled "Systems and Methods for Measuring Birefringence in Glass and Glass-Ceramics" (hereinafter "Roussev II"), discloses apparatus and methods for optically measuring birefringence on the surfaces of glasses and glass-ceramics, including opaque glasses and glass-ceramics. Unlike Roussev I, where separate mode spectra are identified, the method disclosed in Roussev II relies on a careful analysis of the angular intensity distributions for TM and TE light reflected at the prism-sample interface in a prism-coupled measurement format. The contents of the prior application are incorporated herein by reference in their entirety.

[0042] Therefore, the accurate distribution of reflected light intensity versus angle is much more important than in conventional prism-coupled stress measurements, where only the positions of the distinct modes are determined. To this end, the methods disclosed in Roussev I and Roussev II include techniques for normalizing the intensity spectrum, including normalizing to a reference image or signal, correcting for detector nonlinearities, averaging multiple images to reduce image noise and speckle, and applying digital filtering to further smooth the intensity angular spectrum. Moreover, one method includes the formation of a contrast signal, which is additionally normalized to correct for the fundamental difference in shape between the TM and TE signals. The above-mentioned methods rely on obtaining two nearly identical signals and determining their mutual displacement with subpixel resolution by comparing the portions of the signals that contain the steepest regions. The birefringence is proportional to the mutual displacement, and the coefficient depends on the design of the device, including the shape and refractive index of the prism, the focal length of the lens, and the pixel spacing on the sensor. The stress is determined by multiplying the measured birefringence by a known stress-optical coefficient.

[0043] In another disclosed method, after application of some combination of the signal processing techniques described above, the derivatives of the TM and TE signals are determined. The positions of the maximum derivatives of the TM and TE signals are obtained with sub-pixel resolution, and the birefringence is proportional to the spacing of these two maxima, with coefficients determined as described above by the device parameters.

[0044] Related to the requirement for accurate intensity extraction, the device includes several enhancements such as a light scattering surface (static diffuser) close to or on the prism entrance surface to improve the angular uniformity of the illumination, a moving diffuser for speckle reduction when the light source is coherent or partially coherent, and light absorbing coatings on portions of the input and output faces of the prism as well as on the sides of the prism to reduce parasitic background that tends to distort the intensity signal. Additionally, the device may include an infrared light source to enable measurement of opaque materials.

[0045] Furthermore, Roussev II discloses the extinction coefficients and wavelength ranges of the studied samples that can be measured using the described method and device enhancements. s λ<250πσ s wherein α s is the optical attenuation coefficient at the measurement wavelength λ, and σ s is the expected value of the stress to be measured with the precision typically required for practical applications. This wide range allows practically important measurements to be obtained at wavelengths where large optical attenuation makes conventional measurement methods inapplicable. For example, Roussev II discloses successful measurements of stress-induced birefringence in an opaque white glass-ceramic at a wavelength of 1550 nm, where the attenuation is greater than about 30 dB / mm.

[0046] Although it was noted above that there are some problems with the FSM technique at deeper DOL values, FSM is still a useful conventional technique that can be utilized, with the understanding that there may be an error range of up to ±20% at deeper DOL values. As used herein, DOL refers to the depth of the compressive stress layer calculated using the FSM technique, while DOC refers to the depth of the compressive stress layer determined by the method described in Roussev I and II.

[0047] As previously mentioned, the glass-based articles described herein may be chemically strengthened by ion exchange, which exhibits a stress profile different from that exhibited by known strengthened glasses. During this process, ions at or near the surface of the glass-based article are replaced-or exchanged-with larger ions having the same valence or oxidation state. In those embodiments in which the glass-based article comprises an alkali aluminosilicate glass, the ions in the surface layer of the glass and the larger ions are Li + (When present in glass-based articles), Na + , K + , Rb + , and C.S. + Alternatively, the monovalent cations in the surface layer are Ag + In some embodiments, the cations may be replaced with monovalent cations other than alkali metal cations, such as:

[0048] The ion exchange process is generally carried out by immersing the glass-based article in a molten salt bath (or two or more molten salt baths) containing the larger ions to be exchanged for the smaller ions in the glass-based article. It should be noted that aqueous salt baths may also be used. Moreover, the composition of the bath may contain multiple types of larger ions (e.g., Na + and K. +), or a single larger ion. Those skilled in the art will recognize that the parameters of the ion exchange process, including but not limited to the bath composition and temperature, immersion time, number of immersions of the glass-based article in the salt bath (or salt baths), use of multiple salt baths, additional steps such as slow cooling, washing, etc., generally depend on the composition of the glass-based article (including the structure of the article and any crystalline phases present), and the desired DOL or DOC and CS of the glass-based article resulting from the strengthening operation. As an example, ion exchange of the glass-based article may be performed by immersion of the glass-based article in at least one molten bath containing salts such as, but not limited to, nitrates, sulfates, and chlorides of larger alkali metal ions. Typical nitrates include KNO3, NaNO3, LiNO3, and combinations thereof. The temperature of the molten salt bath typically ranges from about 380°C to about 450°C, while the immersion time ranges from about 15 minutes to about 100 hours, depending on the thickness of the glass, the temperature of the bath, and the diffusivity of the glass. However, temperatures and soak times other than those stated above may also be used.

[0049] In one or more embodiments, the glass-based article may be immersed in a molten salt bath of 100% NaNO3 having a temperature of about 370°C to about 480°C. In some embodiments, the glass-based substrate may be immersed in a molten mixed salt bath including about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In some embodiments, the glass-based substrate may be immersed in a molten mixed salt bath including Na2SO4 and NaNO3 and having a wider temperature range (e.g., up to about 500°C). In one or more embodiments, the glass-based article may be immersed in a second bath after immersion in the first bath. Immersion in the second bath may include immersion in a molten salt bath with 100% KNO3 for 15 minutes to 8 hours.

[0050] The ion exchange conditions can be tailored to impart a "spike," i.e., to increase the gradient of the stress profile at or near the surface. This spike can be accomplished with a single bath or multiple baths, where the baths have a single composition or a mixture of compositions, due to the unique nature of the glass compositions used in the glass-based articles described herein.

[0051] As shown in FIG. 3, a glass-based article 300 of one or more embodiments has a first surface 302 and a second surface 304 opposite the first surface that define a thickness t. In one or more embodiments, the thickness t can be about 3 millimeters or less (e.g., in the range of about 0.01 millimeters to about 3 millimeters, about 0.1 millimeters to about 3 millimeters, about 0.2 millimeters to about 3 millimeters, about 0.3 millimeters to about 3 millimeters, about 0.4 millimeters to about 3 millimeters, about 0.01 millimeters to about 2.5 millimeters, about 0.01 millimeters to about 2 millimeters, about 0.01 millimeters to about 1.5 millimeters, about 0.01 millimeters to about 1 millimeter, about 0.01 millimeters to about 0.9 millimeters, about 0.01 millimeters to about 0.8 millimeters, about 0.01 millimeters to about 0.7 millimeters, about 0.01 millimeters to about 0.6 millimeters, about 0.01 millimeters to about 0.5 millimeters, about 0.1 millimeters to about 0.5 millimeters, or about 0.3 millimeters to about 0.5 millimeters).

[0052] The glass-based article has a stress profile that extends from a first surface 302 to a second surface 304 (or along the entire thickness, t). In the embodiment shown in Figure 3, a stress profile 312 as measured by Roussev I and II as described herein is shown along with a stress profile 340 estimated by FSM measurement techniques as described herein. The x-axis represents stress values ​​and the y-axis represents depth or thickness within the glass-based article.

[0053] As shown in FIG. 3 , the stress profile 312 shows a CS layer 315 (having a surface CS 310), a CT layer 325 (having a maximum CT 320), and a DOC 317 where the stress profile 312 goes from compressive to tensile at 330. The CT layer 325 also has an associated depth or length 327 (CT region or layer). The estimated stress profile 340 shows a DOL that is greater than the DOC. As used herein, references to DOC and DOL refer to respective depths from one surface (either the first surface 302 or the second surface 304) with the understanding that such DOC or DOL may exist from the other surface.

[0054] Surface CS 310 can be about 150 MPa or more, or about 200 MPa or more (e.g., about 250 MPa or more, about 300 MPa or more, about 400 MPa or more, about 450 MPa or more, about 500 MPa or more, or about 550 MPa or more). Surface CS 310 can be up to about 900 MPa, up to about 1000 MPa, up to about 1100 MPa, or up to about 1200 MPa. Maximum CT 320 can be about 25 MPa or more, about 50 MPa or more, or about 100 MPa or more (e.g., about 150 MPa or more, about 200 MPa or more, about 250 MPa or more, or about 300 MPa or more). In some embodiments, the maximum CT 320 may range from about 50 MPa to about 250 MPa (e.g., from about 75 MPa to about 250 MPa, from about 100 MPa to about 250 MPa, from about 150 MPa to about 250 MPa, from about 50 MPa to about 175 MPa, from about 50 MPa to about 150 MPa, or from about 50 MPa to about 100 MPa). The maximum CT 320 may be located in a range from about 0.3·t to about 0.7·t, from about 0.4·t to about 0.6·t, or from about 0.45·t to about 0.55·t. It should be noted that any one or more of the surface CS 310 and the maximum CT 320 will depend on the thickness of the glass-based article. For example, a glass-based article having a thickness of about 0.8 mm may have a maximum CT of about 100 MPa or more. As the thickness of the glass-based article decreases, the maximum CT may increase. In other words, the maximum CT increases as the thickness decreases (i.e., as the glass-based article becomes thinner).

[0055] In some embodiments, the ratio of maximum CT 320 to surface CS 310 may be in the range of about 0.05 to about 1 (e.g., in the range of about 0.05 to about 0.5, about 0.05 to about 0.3, about 0.05 to about 0.2, about 0.05 to about 0.1, about 0.5 to about 0.8, about 0.5 to about 1, about 0.2 to about 0.5, about 0.3 to about 0.5). In known chemically strengthened glass-based articles, the ratio of maximum CT 320 to surface CS 310 is 0.1 or less. In some embodiments, the surface CS may be 1.5 times (or 2 times or 2.5 times) or more the maximum CT. In some embodiments, the surface CS may be up to about 20 times the maximum CT.

[0056] In one or more embodiments, the stress profile 312 has a maximum CS, which is generally at a surface CS 310 and is found at one or both of the first surface 302 and the second surface 304. In one or more embodiments, the CS layer or region 315 extends along a portion of the thickness to the DOC 317. In one or more embodiments, the DOC 317 can be about 0.1·t or greater. For example, the DOC 317 can be about 0.12·t or greater, about 0.14·t or greater, about 0.15·t or greater, about 0.16·t or greater, about 0.17·t or greater, about 0.18·t or greater, about 0.19·t or greater, about 0.20·t or greater, about 0.21·t or greater, or about 0.25·t or greater. In some embodiments, the DOC 317 is less than the chemical depth 342. The chemical depth 342 may be about 0.4·t or greater, about 0.5·t or greater, about 0.55·t or greater, or about 0.6·t or greater. In one or more embodiments, the stress profile 312 may be described as parabolic in shape. In some embodiments, the stress profile along the depth or region of the glass-based article exhibiting tensile stress exhibits a parabolic shape. In one or more particular embodiments, the stress profile 312 is free of flat stress (i.e., compressive or tensile) portions or portions exhibiting substantially constant stress (i.e., compressive or tensile). In some embodiments, the CT region exhibits a stress profile that is substantially free of flat stress or substantially constant stress. In one or more embodiments, all points of the stress profile 312 between the thickness ranges of about 0·t to about 0.2·t and greater than 0.8·t (or about 0·t to about 0.3·t and greater than 0.7·t) have a tangent less than about -0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer. In some embodiments, the tangent may be less than about -0.2 MPa / micrometer or greater than about 0.2 MPa / micrometer. In some more particular embodiments, the tangent may be less than about -0.3 MPa / micrometer or greater than about 0.3 MPa / micrometer. In even more particular embodiments, the tangent may be less than about -0.5 MPa / micrometer or greater than about 0.5 MPa / micrometer.In other words, the stress profile of one or more embodiments along these thickness ranges (i.e., from about 0·t to about 0.2·t and greater than 0.8·t, or from about 0·t to about 0.3·t and greater than 0.7·t) excludes points with tangents as described herein. Without being bound by theory, known error functions or quasi-linear stress profiles have points along these thickness ranges (i.e., from about 0·t to about 0.2·t and greater than 0.8·t, or from about 0·t to about 0.3·t and greater than 0.7·t) with tangents of about -0.1 MPa / micrometer to about 0.1 MPa / micrometer, about -0.2 MPa / micrometer to about 0.2 MPa / micrometer, about -0.3 MPa / micrometer to about 0.3 MPa / micrometer, or about -0.5 MPa / micrometer to about 0.5 MPa / micrometer (indicating a flat or zero gradient stress profile along such thickness ranges, as shown at 220 in FIG. 2). The stress profile of one or more embodiments of the present disclosure does not exhibit such a stress profile, as shown in FIG. 3, having a flat or zero gradient stress profile along these thickness ranges.

[0057] In one or more embodiments, the glass-based article exhibits a stress profile having a maximum tangent and a minimum tangent in the thickness ranges of about 0.1·t to 0.3·t and about 0.7·t to 0.9·t. In some cases, the difference between the maximum tangent and the minimum tangent is about 3.5 MP / micrometer or less, about 3 MP / micrometer or less, about 2.5 MP / micrometer or less, or about 2 MP / micrometer or less.

[0058] In one or more embodiments, the stress profile 312 is substantially free of any linear segments extending along the depth of the glass-based article, or along at least a portion of the thickness t. In other words, the stress profile 312 increases or decreases substantially continuously along the thickness t. In some embodiments, the stress profile is substantially free of any linear segments in the depth direction having a length of about 10 micrometers or more, about 50 micrometers or more, or about 100 micrometers or more, or about 200 micrometers or more. As used herein, the term "linear" refers to a gradient along the linear segment having a magnitude of less than about 5 MPa / micrometer, or less than about 2 MPa / micrometer. In some embodiments, one or more portions of the stress profile that are substantially free of any linear segments in the depth direction are present at a depth within the glass-based article of about 5 micrometers or more (e.g., 10 micrometers or more, or 15 micrometers or more) from either or both of the first surface or the second surface. For example, along a depth of about 0 micrometers to less than about 5 micrometers from the first surface, the stress profile may include a linear segment, but from a depth of about 5 micrometers or more from the first surface, the stress profile may be substantially free of linear segments.

[0059] In some embodiments, the stress profile may include a linear segment from a depth of about 0t to about 0.1t, and may be substantially free of a linear segment from a depth of about 0.1t to about 0.4t. In some embodiments, the stress profile in the thickness range of about 0t to about 0.1t may have a gradient in the range of about 20 MPa / micrometer to about 200 MPa / micrometer. As described herein, such embodiments may be formed using a single ion exchange process, whereby the bath includes two or more alkali salts or is a mixed alkali salt bath, or multiple (e.g., two or more) ion exchange processes.

[0060] In one or more embodiments, the glass-based article may be described in terms of the shape of the stress profile along the CT region (327 in FIG. 3). For example, in some embodiments, the stress profile along the CT region (where the stress is tensile) may be approximated by the formula: In some embodiments, the stress profile along the CT region may be approximated by Equation (1):

[0061]

number

[0062] In equation (1), Stress(x) is the stress value at location x, where Stress is positive (tension). MaxCT is the maximum central tension as a positive value expressed in MPa. The value x is the location along the thickness (t) in micrometers and ranges from 0 to t; x=0 is one surface (302 in FIG. 3), x=0.5 is the center of the glass-based article, and Stress(x)=MaxCT, x=t is the opposite surface (304 in FIG. 3). The MaxCT used in equation (1) can range from about 50 MPa to about 350 MPa (e.g., 60 MPa to about 300 MPa, or about 70 MPa to about 270 MPa), and n is an approximation parameter from 1.5 to 5 (e.g., 2 to 4, 2 to 3, or 1.8 to 2.2), whereby n=2 can give a parabolic stress profile, and exponents that deviate from n=2 give the stress profile a near-parabolic stress profile. Figure 39 shows example stress profiles for various combinations of MaxCT and n (1.5 to 5 as indicated in the legend) for a 0.8 mm thick glass-based article.

[0063] In some embodiments, the stress profile may be altered by heat treatment. In such embodiments, the heat treatment may occur before any ion-exchange process, during any ion-exchange process, or after all ion-exchange processes. In some embodiments, the heat treatment may reduce the slope of the stress profile at or near the surface. In some embodiments where a steeper or larger slope is desired at the surface, an ion-exchange process after the heat treatment may be used to provide a "spike" at or near the surface, i.e., increase the slope of the stress profile.

[0064] In one or more embodiments, the stress profile 312 (and / or estimated stress profile 340) arises due to a non-zero concentration of metal oxide that varies along a portion of the thickness. The variation in concentration may be referred to herein as a gradient. In some embodiments, the concentration of metal oxide varies non-zero along a thickness range of about 0·t to about 0.3·t. In some embodiments, the concentration of metal oxide varies non-zero along a thickness range of about 0·t to about 0.35·t, about 0·t to about 0.4·t, about 0·t to about 0.45·t, or about 0·t to about 0.48·t. The metal oxide may be described as inducing stress in the glass-based article. The variation in concentration may be continuous along the thickness range described above. The variation in concentration may include a change of about 0.2 mol % of metal oxide concentration along a thickness segment of about 100 micrometers. This change may be measured by methods known in the art, including a microprobe, as shown in Example 1. Metal oxides that have a non-zero concentration and that vary along a portion of the thickness may be described as causing stress in the glass-based article.

[0065] The variation in concentration may be continuous along the thickness ranges mentioned above. In some embodiments, the variation in concentration may be continuous along a thickness segment ranging from about 10 micrometers to about 30 micrometers. In some embodiments, the concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface, and increases from that point to the second surface.

[0066] The metal oxide concentration may include multiple metal oxides (e.g., a combination of Na2O and KO). In some embodiments where two metal oxides are utilized and the radii of the ions are different, the concentration of the ions with the larger radius is greater than the concentration of the ions with the smaller radius at shallow depths, while at greater depths the concentration of the smaller ions with the larger radius is greater than the concentration of the ions with the larger radius. For example, if a single Na-containing bath and a K-containing bath are used in the ion exchange process, the concentration of K in the glass-based article may be greater than the concentration of the smaller ions with the larger radius. + The concentration of ions at shallower depths is Na + ions, whereas at greater depths, Na + The concentration of the ion is K + The concentration of ions is greater than the concentration of ions at the surface, due in part to the size of the ions. In such glass-based articles, areas at or near the surface have a greater CS due to a greater amount of larger ions at or near the surface. This greater CS would be manifested by a stress profile at or near the surface having a steeper gradient (i.e., a spike in the stress profile at the surface).

[0067] The concentration gradient or variation of one or more metal oxides is produced, for example, by chemically strengthening the glass-based article by an ion exchange process as previously described herein, in which a plurality of first metal ions in the glass-based article are exchanged for a plurality of second metal ions. The first metal ions may be ions of lithium, sodium, potassium, and rubidium. The second metal ions may be ions of one of sodium, potassium, rubidium, and cesium, provided that the second alkali metal ion has an ionic radius larger than the ionic radius of the first alkali metal ion. The second metal ion is present in the glass-based substrate as its oxide (e.g., Na2O, KO, Rb2O, Cs2O, or combinations thereof).

[0068] In one or more embodiments, the concentration gradient of the metal oxide extends through a substantial portion of the thickness t or the entire thickness t of the glass-based article including the CT layer 325. In one or more embodiments, the concentration of the metal oxide is about 0.5 mol % or greater in the CT layer 325. In some embodiments, the concentration of the metal oxide may be about 0.5 mol % or greater (e.g., about 1 mol % or greater) along the entire thickness of the glass-based article, is greatest at the first surface 302 and / or the second surface 304, and decreases substantially constantly to a point between the first surface 302 and the second surface 304. At that point, the concentration of the metal oxide is a minimum along the entire thickness t; however, the concentration is also non-zero at that point. In other words, the non-zero concentration of that particular metal oxide extends through a substantial portion of the thickness t (as described herein) or the entire thickness t. In some embodiments, the minimum concentration of that particular metal oxide is in the CT layer 327. The total concentration of a particular metal oxide in the glass-based article may range from about 1 mol % to about 20 mol %.

[0069] In one or more embodiments, the glass-based article has a first metal oxide concentration and a second metal oxide concentration, where the first metal oxide concentration ranges from about 0 mol% to about 15 mol% along a first thickness range of about 0t to about 0.5t and the second metal oxide concentration ranges from about 0 mol% to about 10 mol% along a second thickness range of about 0 micrometers to about 25 micrometers (or about 0 micrometers to about 12 micrometers). The glass-based article may have an optional third metal oxide concentration. The first metal oxide may include Na2O and the second metal oxide may include KO.

[0070] The concentration of said metal oxide may be determined from a baseline amount of metal oxide in the glass-based article before it is altered to include a concentration gradient of such metal oxide.

[0071] In one or more embodiments, the glass-based articles may be described in terms of how they break and the fragments resulting from such breakage. In one or more embodiments, the glass-based article, when broken, breaks into 2 or more fragments per square inch (or per 6.4516 square centimeters). In some cases, the glass-based article breaks into 3 or more, 4 or more, 5 or more, or 10 or more fragments per square inch (or per 6.4516 square centimeters) of the glass-based article (before breaking). In some cases, the glass-based article, when broken, breaks into fragments such that 50% or more of the fragments have a surface area that is less than 5%, less than 2%, or less than 1% of the surface area of ​​the glass-based article (before breaking). In some embodiments, the glass-based article, when broken, breaks into fragments such that 90% or more or even 100% of the fragments have a surface area that is less than 5%, less than 2%, or less than 1% of the surface area of ​​the glass-based article (before breaking).

[0072] In one or more embodiments, after the glass-based article is chemically strengthened, the resulting stress profile 312 (and estimated stress profile 340) of the glass-based article provides improved fracture resistance. For example, in some embodiments, the glass-based article, upon fracture, includes fragments having an average longest cross-sectional dimension of about 2·t or less (e.g., 1.8·t, 1.6·t, 1.5·t, 1.4·t, 1.2·t, or 1·t or less).

[0073] In one or more embodiments, the glass-based article has a compressibility of about 0.7 MPa m 1 / 2 Fracture toughness (K 1C In some cases, the fracture toughness is approximately 0.8 MPa m 1 / 2 or more, or approximately 0.9 MPa m 1 / 2 In some embodiments, the fracture toughness is about 0.7 MPa m 1 / 2 to about 1 MPa m 1 / 2 may be in the range of

[0074] In some embodiments, the substrate may be characterized as having a hardness of about 500 HVN to about 800 HVN, as measured by the Vickers Hardness Test at a load of 200 g.

[0075] The glass-based articles described herein have a thermal conductivity of 0 J / m 2 From over 20 J / m 2 In some cases, the stored tensile energy is about 1 J / m 2 from about 20 J / m 2 , about 2J / m 2 from about 20 J / m 2 , about 3J / m 2 from about 20 J / m 2 , about 4J / m 2 from about 20 J / m 2 , about 1J / m 2 from about 19 J / m 2 , about 1J / m 2 from about 18 J / m 2 , about 1J / m 2 from about 16 J / m2 , about 4J / m 2 from about 20 J / m 2 , or about 4 J / m 2 from about 18 J / m 2 The stored tensile energy can be in the range of 0.01 to 0.05, as expressed by Equation (2):

[0076]

number

[0077] is formed by integrating the stored elastic energy Σ per unit area of ​​a sample of thickness t in the tensile region using the formula:

[0078] More specifically, the stored tensile energy is calculated according to the following formula (3):

[0079]

number

[0080] where n is the Poisson's ratio, E is the elastic modulus, and the integral is calculated over the tensile region only.

[0081] In one or more embodiments, the glass-based article exhibits improved surface strength when subjected to the Abraded Ring-on-Ring (AROR) test. The strength of the material is defined as the stress at which fracture occurs. The A-ROR test is a surface strength measurement for testing flat glass specimens, and ASTM C1499-09(2013), entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature," serves as the basis for the Ring-on-Ring Abraded ROR test method described herein. The contents of ASTM C1499-09 are incorporated herein by reference in their entirety. In one embodiment, the glass specimens are abraded with 90 grit silicon carbide (SiC) particles delivered to the glass sample prior to ring-on-ring testing using the methods and apparatus described in Annex A2, entitled "Abrasion Procedures," of ASTM C158-02(2012), entitled "Standard Test Methods for Strength of Glass by Flexure (Determination of Modulus of Rupture)." The contents of ASTM C158-02 and, in particular, Annex 2, are hereby incorporated by reference in their entirety.

[0082] Prior to ring-on-ring testing, the surface of the glass-based article is abraded as described in ASTM C158-02, Annex 2, using the apparatus shown in Figure A2.1 of ASTM C158-02 to standardize and / or control the surface defect condition of the samples. The abrasive is blown onto the surface 110 of the glass-based article at a load of 15 psi (about 103 kPa) using an air pressure of 304 kPa (44 psi); however, in the examples below, the abrasive was blown onto the surface 110 at loads of 25 psi (about 172 kPa) and 45 psi (about 310 kPa). After the airflow was established, the abrasive was blown onto the surface 110 at a load of 5 cm. 3 of abrasive is placed into the funnel and the sample is sandblasted for 5 seconds after the introduction of the abrasive.

[0083] For ring-on-ring testing, a glass sample 410 having at least one polished surface as shown in Figure 4 is placed between two concentric rings of different sizes, also as shown in Figure 4, to determine the equibiaxial bending strength (i.e., the maximum stress the material can sustain when subjected to bending between two concentric rings). In the ring-on-ring as polished configuration 400, the polished glass-based article 410 is supported by a support ring 420 having a diameter D2. A force F is applied by a load cell (not shown) to the surface of the glass-based article by a loading ring 430 having a diameter D1.

[0084] The diameter ratio D1 / D2 of the load ring to the support ring may range from about 0.2 to about 0.5. In some embodiments, D1 / D2 is about 0.5. The load and support rings 430, 420 should be concentrically aligned to within 0.5% of the support ring diameter D2. The load cell used for testing should be accurate to within ±1% at any load within the selected range. In some embodiments, testing is performed at a temperature of 23±2° C. and a relative humidity of 40±10%.

[0085] For the design of the instrument, the radius r of the protruding surface of the loading ring 430 is h / 2≦r≦3h / 2, where h is the thickness of the glass-based article 410. The loading and support rings 430, 420 are generally made of a material having a hardness of HR c > Made from hardened steel 40. ROR instruments are commercially available.

[0086] The objective failure mechanism of the ROR test is to observe the cracking of the glass-based article 410 originating from the surface 430a within the loading ring 430. Any failures occurring outside of this region - i.e., between the loading ring 430 and the support ring 420 - are excluded from the data analysis. However, due to the thinness and high strength of the glass-based article 410, large deflections exceeding ½ of the thickness h of the specimen can be observed. Thus, it is not uncommon to observe a high percentage of failures originating from below the loading ring 430. Without knowing the stress development both inside and below the ring (collected by strain gauge analysis) and the initiation point of failure in each specimen, the stress cannot be calculated accurately. Therefore, the AROR test focuses on the maximum load at failure as the measured response.

[0087] The strength of glass-based articles depends on the presence of surface flaws. However, because the strength of glass is statistical in nature, the tendency for a flaw of a given size to be present cannot be accurately predicted. Therefore, a probability distribution can generally be used as a statistical representation of the data obtained.

[0088] In some embodiments, the reinforced glass-based articles described herein have a surface or equibiaxial flexural strength of at least 20 kgf (about 196 N) and up to about 30 kgf (about 294 N) as determined by abraded ring-on-ring testing using a load of 25 psi (about 172 kPa) or even 45 psi (about 310 kPa) to abrade the surface. The surface strength is at least 25 kgf (about 245 N) in other embodiments, and at least 30 kgf (about 294 N) in still other embodiments.

[0089] In some embodiments, the reinforced glass-based articles described herein may be described in terms of their performance in an Inverted Ball on Sandpaper (IBoS) test. The IBoS test is a dynamic component-level test that mimics the dominant mechanism of failure due to bending that typically occurs in glass-based articles used in portable or handheld electronic devices, as shown generally in FIG. 36, in addition to the introduction of damage. In the field, the introduction of damage occurs at the top surface of the glass-based article (FIG. 37a). A crack initiates at the top surface of the glass-based article and either the damage penetrates the glass-based article (FIG. 37b) or the crack propagates from the bending of the top surface or from within the glass-based article (FIG. 37c). The IBoS test is designed to simultaneously introduce damage to the surface of the glass and apply bending under dynamic load. In some cases, the glass-based article exhibits improved drop performance when it contains compressive stresses over the same glass-based article without the compressive stresses.

[0090] The IBoS testing apparatus is shown generally in FIG. 36. The apparatus 500 includes a test stand 510 and a ball 530. The ball 530 is a rigid or solid ball, such as, for example, a stainless steel ball. In one embodiment, the ball 530 is a stainless steel ball with a diameter of 10 mm and weighing 4.2 grams. The ball 530 is dropped directly onto the glass-based article sample 518 from a predetermined height h. The test stand 510 includes a solid base 512 made of a hard, rigid material, such as granite. A sheet 514 having an abrasive surface is placed on top of the solid base 512 with the abrasive surface facing upwards. The sheet 514 is an abrasive paper with a 30 grit surface in some embodiments and a 180 grit surface in other embodiments. The glass-based article sample 518 is held in place on the sheet 514 by a sample holder 515 such that there is an air gap 516 between the glass-based article sample 518 and the sheet 514. An air gap 516 between the glass sheet 514 and the glass-based article sample 518 allows the glass-based article sample 518 to bend upon impact of the ball 530 on the polished surface of the sheet 514. In one embodiment, the glass-based article sample 518 is clamped at all corners to ensure repeatability, with bending restricted only to the point of impact of the ball. In some embodiments, the sample holder 515 and test stand 510 are adapted to accommodate sample thicknesses up to about 2 mm. The air gap 516 is in the range of about 50 μm to about 100 μm. The air gap 516 is adapted to adjust for differences in material stiffness (Young's modulus, EMod), including the elastic modulus and thickness of the sample. An adhesive tape 520 may be used to cover the top surface of the glass-based article sample to collect debris in the event of a breakage of the glass-based article sample 518 upon impact of the ball 530.

[0091] A variety of materials may be used as the abrasive surface. In one particular embodiment, the abrasive surface is an abrasive paper, such as silicon carbide or alumina paper, industrial abrasive paper, or any abrasive known to those skilled in the art to have a similar hardness and / or sharpness. In some embodiments, abrasive paper having 30 grit may be used, as it has a more consistent surface topography than either concrete or asphalt, as well as a grain size and sharpness that produces the desired level of surface damage to the sample.

[0092] In one embodiment, a method 600 of performing an IBoS test using the apparatus 500 described above is shown in FIG. 38. In step 610, a glass-based article sample (518 in FIG. 36) as described above and secured to a sample holder 515 is placed in a test stand 510 such that a gap 516 is formed between the glass-based article sample 518 and the sheet 514 having an abrasive surface. The method 600 assumes that the sheet 514 having an abrasive surface has already been placed in the test stand 510. However, in some embodiments, the method may include placing the sheet 514 in the test stand 510 such that the surface having the abrasive is facing upwards. In some embodiments (step 610a), an adhesive tape 520 is applied to the top surface of the glass-based article sample 518 prior to securing the glass-based article sample 518 to the sample holder 515.

[0093] In step 620, a solid ball 530 of a predetermined mass and size is dropped from a predetermined height h onto the top surface of the glass-based article sample 518 such that the ball 530 impacts the top surface approximately at the center of the top surface (i.e., within 1 mm, or within 3 mm, or within 5 mm, or within 10 mm of the center). After impact in step 620, the extent of damage to the glass-based article sample 518 is determined (step 630). As previously noted, the term "crack" herein means that a crack propagates through the entire thickness and / or surface of a substrate when the substrate is dropped or impacted by an object.

[0094] In method 600, the sheet 514 having an abrasive surface may be replaced after each drop to avoid the "age" hardening that has been observed with repeated use of other types of drop test surfaces (e.g., concrete or asphalt).

[0095] Various predetermined drop heights h and increments are typically used in method 600. The test may, for example, begin with a minimum drop height (e.g., about 10-20 cm). This height may then be increased for successive drops by either a prescribed increment or a variable increment. The test described in method 600 stops once the glass-based article sample 518 breaks or cracks (step 631). Alternatively, the drop test of method 600 may stop once the drop height h reaches a maximum drop height (e.g., about 100 cm) without cracking, or step 620 may be repeated at that maximum height until cracks occur.

[0096] In some embodiments, the IBoS test of method 600 is performed only once on each glass-based article sample 518 at each given height h. However, in other embodiments, multiple tests may be performed on each sample at each height.

[0097] If cracks occur in the glass-based article sample 518 (step 631 in FIG. 38), IBoS testing according to method 600 ends (step 640). If no cracks are observed upon dropping the ball at the predetermined drop height (step 632), the drop height is increased by a predetermined increment (step 634), e.g., 5, 10, or 20 cm, and steps 620 and 630 are repeated until either cracks are observed in the sample (step 631) or the maximum test height is reached without the sample cracking (step 636). Once either step 631 or 636 is reached, testing according to method 600 ends.

[0098] When subjected to the Inverted Ball on Sandpaper (IBoS) test described above, embodiments of the glass-based articles described herein have a survival rate of at least about 60% when a ball is dropped onto a glass surface from a height of 100 cm. For example, a glass-based article is described as having a 60% survival rate when dropped from a given height (here, 100 cm) if three out of five identical (or nearly identical) samples (i.e., having nearly the same composition and, when tempered as described herein, having nearly the same compressive stress and compressive or compressive stress layer depth) survive the IBoS test without cracking. In other embodiments, the survival rate of the tempered glass-based article in the 100 cm IBoS test is at least about 70%, in other embodiments at least about 80%, and in still other embodiments at least about 90%. In other embodiments, the survival rate of a reinforced glass-based article dropped from a height of 100 cm in the IBoS test is at least about 60%, in other embodiments at least about 70%, in yet other embodiments at least about 80%, and in other embodiments at least about 90%. In one or more embodiments, the survival rate of a reinforced glass-based article dropped from a height of 150 cm in the IBoS test is at least about 60%, in other embodiments at least about 70%, in yet other embodiments at least about 80%, and in other embodiments at least about 90%.

[0099] To determine the survival rate of a glass-based article when dropped from a predetermined height using the IBoS test method and apparatus described above, at least five identical (or nearly identical) samples of the glass-based article (i.e., having about the same composition and about the same compressive stress and compression or depth of layer) are tested, although a greater number of samples (e.g., 10, 20, 30, etc.) may be tested to increase the confidence level of the test results. Each sample is dropped once from the predetermined height (e.g., 100 cm or 150 cm) or dropped from progressively higher heights without breaking until the predetermined height is reached and visually (i.e., with the naked eye) examined for evidence of cracking (the formation and propagation of a crack through the entire thickness and / or surface of the sample). If no cracks are observed after the drop from the predetermined height, the sample is considered to have "survived" the drop test, and if cracks are observed when the sample is dropped from a height equal to or less than the predetermined height, the sample is considered to have "failed" (or "did not survive"). Survival is determined to be the percentage of the sample population that survives the drop test. For example, if 7 samples out of a group of 10 samples do not break when dropped from a given height, the survival rate of the glass would be 70%.

[0100] The glass-based articles described herein may be transparent or opaque. In one or more embodiments, the glass-based articles may have a thickness of about 1 millimeter or less and exhibit a transmittance of about 88% or more over a wavelength range of about 380 nm to about 780 nm. In other embodiments, the glass-based articles may have a thickness of about 1 millimeter or less and exhibit a transmittance of about 10% or less over a wavelength range of about 380 nm to about 780 nm.

[0101] The glass-based article may also exhibit a substantially white color. For example, the glass-based article may have an L of about 88 or greater under CIE illuminant F02. * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 *Alternatively, the glass-based article may have a CIELAB color space coordinate system with an L value of about 40 or less under CIE illuminant F02. * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 * The CIELAB color space coordinates of the color value may exist under other CIE illuminants (e.g., D65).

[0102] The choice of substrate is not particularly limited. In some instances, the glass-based article may be described as having high cation diffusivity due to ion exchange. In one or more embodiments, the glass or glass ceramic has fast ion exchange capability, i.e., a diffusivity of 500 μm or more. 2 / hr or 450μm at 460℃ 2 / time over.

[0103] At a particular temperature, the diffusivity is given by Equation (4):

[0104]

number

[0105] where DOL is the depth of the ion exchange layer and T is the ion exchange time it takes to reach that DOL.

[0106] The glass-based article may include an amorphous substrate, a crystalline substrate, or a combination thereof (e.g., a glass-ceramic substrate). In one or more embodiments, the substrate of the glass-based article (before being chemically strengthened as described herein) may include a glass having a composition, expressed in mole percent (mol%), including SiO2 in the range of about 40 to about 80, Al2O3 in the range of about 10 to about 30, B2O3 in the range of about 0 to about 10, RO in the range of about 0 to about 20, and RO in the range of about 0 to about 15. In some cases, the composition may include either or both of ZrO2 in the range of about 0 mol% to about 5 mol% and P2O5 in the range of about 0 mol% to about 15 mol%. TiO2 may be present at about 0 mol% to about 2 mol%.

[0107] In some embodiments, the glass composition may include SiO in an amount, expressed in mole percent, ranging from about 45 to about 80, from about 45 to about 75, from about 45 to about 70, from about 45 to about 65, from about 45 to about 60, from about 50 to about 70, from about 55 to about 70, from about 60 to about 70, from about 70 to about 75, from about 70 to about 72, or from about 50 to about 65.

[0108] In some embodiments, the glass composition may include Al2O3 in an amount, expressed in mole percent, ranging from about 5 to about 28, from about 5 to about 26, from about 5 to about 25, from about 5 to about 24, from about 5 to about 22, from about 5 to about 20, from about 6 to about 30, from about 8 to about 30, from about 10 to about 30, from about 12 to about 30, from about 14 to about 30, from about 16 to about 30, from about 18 to about 30, from about 18 to about 28, or from about 12 to about 15.

[0109] In one or more embodiments, the glass composition may include B2O3 in an amount, expressed in mole percent, ranging from about 0 to about 8, about 0 to about 6, about 0 to about 4, about 0.1 to about 8, about 0.1 to about 6, about 0.1 to about 4, about 1 to about 10, about 2 to about 10, about 4 to about 10, about 2 to about 8, about 0.1 to about 5, or about 1 to about 3. In some cases, the glass composition may be substantially free of B2O3. As used herein, the phrase "substantially free" with respect to a component of a glass composition means that the component is not actively or intentionally added to the glass composition during initial batch formulation or subsequent ion exchange, but may be present as an impurity. For example, a glass may be described as substantially free of a component if the component is present in an amount less than about 0.1001 mole percent.

[0110] In some embodiments, the glass composition may include one or more alkaline earth metal oxides, such as MgO, CaO, and ZnO. In some embodiments, the total amount of the one or more alkaline earth metal oxides may be from a non-zero amount to about 15 mol%. In one or more particular embodiments, the total amount of any of the alkaline earth metal oxides may be from a non-zero amount to about 14 mol%, to about 12 mol%, to about 10 mol%, to about 8 mol%, to about 6 mol%, to about 4 mol%, to about 2 mol%, or to about 1.5 mol%. In some embodiments, the total amount of the one or more alkaline earth metal oxides, expressed in mol%, may range from about 0.1 to 10, about 0.1 to 8, about 0.1 to 6, about 0.1 to 5, about 1 to 10, about 2 to 10, or about 2.5 to 8. The amount of MgO may range from about 0 mol% to about 5 mol% (e.g., about 2 mol% to about 4 mol%). The amount of ZnO may range from about 0 mol% to about 2 mol%. The amount of CaO may range from about 0 mol% to about 2 mol%. In one or more embodiments, the glass composition may include MgO and may be substantially free of CaO and ZnO. In one variation, the glass composition may include either CaO or ZnO and may be substantially free of the others of MgO, CaO, and ZnO. In one or more particular embodiments, the glass composition may include only two of the alkaline earth metal oxides MgO, CaO, and ZnO and may be substantially free of the third alkaline earth metal oxide.

[0111] The total amount of alkali metal oxides, R2O, in the glass composition, expressed in mole percent, can be in the range of about 5 to about 20, about 5 to about 18, about 5 to about 16, about 5 to about 15, about 5 to about 14, about 5 to about 12, about 5 to about 10, about 5 to about 8, about 6 to about 20, about 7 to about 20, about 8 to about 20, about 9 to about 20, about 10 to about 20, about 6 to about 13, or about 8 to about 12.

[0112] In one or more embodiments, the glass composition includes NaO in an amount ranging from about 0 mol% to about 18 mol%, about 0 mol% to about 16 mol%, about 0 mol% to about 14 mol%, about 0 mol% to about 10 mol%, about 0 mol% to about 5 mol%, about 0 mol% to about 2 mol%, about 0.1 mol% to about 6 mol%, about 0.1 mol% to about 5 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, or about 10 mol% to about 20 mol%.

[0113] In some embodiments, the amounts of Li2O and Na2O are controlled to specific amounts or ratios to balance formability and ion-exchangeability. For example, as the amount of Li2O is increased, the liquidus viscosity may decrease, thereby making certain forming methods unusable; however, such glass compositions may be ion-exchanged to deeper DOC levels as described herein. The amount of Na2O can change the liquidus viscosity, but may inhibit ion-exchange to deeper DOC levels.

[0114] In one or more embodiments, the glass composition may include KO in an amount less than about 5 mol%, less than about 4 mol%, less than about 3 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more alternative embodiments, the glass composition may be substantially free of KO, as defined herein.

[0115] In one or more embodiments, the glass composition may include Li2O in an amount of about 0 mol% to about 18 mol%, about 0 mol% to about 15 mol%, or about 0 mol% to about 10 mol%, about 0 mol% to about 8 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 4 mol%, or about 0 mol% to about 2 mol%. In some embodiments, the glass composition may include Li2O in an amount of about 2 mol% to about 10 mol%, about 4 mol% to about 10 mol%, about 6 mol% to about 10 mol%, or about 5 mol% to about 8 mol%. In one or more alternative embodiments, the glass composition may be substantially free of Li2O, as defined herein.

[0116] In one or more embodiments, the glass composition may include Fe2O3. In such embodiments, Fe2O3 may be present in an amount less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol%, and all ranges and sub-ranges therebetween. In one or more alternative embodiments, the glass composition may be substantially free of Fe2O3, as defined herein.

[0117] In one or more embodiments, the glass composition may include ZrO2. In such embodiments, ZrO2 may be present in an amount less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol%, and all ranges and sub-ranges therebetween. In one or more alternative embodiments, the glass composition may be substantially free of ZrO2, as defined herein.

[0118] In one or more embodiments, the glass composition may include P2O5 in the range of about 0 mol% to about 10 mol%, about 0 mol% to about 8 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 4 mol%, about 0.1 mol% to about 10 mol%, about 0.1 mol% to about 8 mol%, about 4 mol% to about 8 mol%, or about 5 mol% to about 8 mol%. In some cases, the glass composition may be substantially free of P2O5.

[0119] In one or more embodiments, the glass composition may include TiO2. In such embodiments, TiO2 may be present in an amount less than about 6 mol%, less than about 4 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more alternative embodiments, the glass composition may be substantially free of TiO2, as defined herein. In some embodiments, TiO2 is present in an amount ranging from about 0.1 mol% to about 6 mol%, or from about 0.1 mol% to about 4 mol%.

[0120] In some embodiments, the glass composition may include various compositional relationships. For example, the glass composition may include a ratio of the amount (mol %) of Li2O to the total amount (mol %) of R2O ranging from about 0.5 to about 1. In some embodiments, the glass composition may include a difference in the total amount (mol %) of R2O to the amount (mol %) of Al2O3 ranging from about -5 to about 0. In some cases, the glass composition may include a difference in the total amount (mol %) of R2O to the amount (mol %) of Al2O3 ranging from about 0 to about 3. x The glass composition of one or more embodiments may exhibit a ratio of the amount of MgO (mol %) to the total amount of RO (mol %) ranging from about 0 to about 2.

[0121] In some embodiments, the glass composition may be substantially free of nucleating agents. Typical examples of nucleating agents include TiO2, ZrO2, etc. Nucleating agents may be described in terms of their function as components in a glass that can initiate the formation of crystallites in the glass.

[0122] In some embodiments, the composition used in the glass substrate may include 0-2 mol % of at least one fining agent selected from the group including Na2SO4, NaCl, NaF, NaBr, K2SO4, KCl, KF, KBr, and SnO2. The glass composition according to one or more embodiments may further include SnO2 in the range of about 0 to about 2, about 0 to about 1, about 0.1 to about 2, about 0.1 to about 1, or about 1 to about 2. The glass compositions disclosed herein may be substantially free of As2O3 and / or Sb2O3.

[0123] In one or more embodiments, the composition may comprise 62 mol% to 75 mol% SiO2, 10.5 mol% to about 17 mol% Al2O3, 5 mol% to about 13 mol% Li2O, 0 mol% to about 4 mol% ZnO, 0 mol% to about 8 mol% MgO, 2 mol% to about 5 mol% TiO2, 0 mol% to about 4 mol% B2O3, 0 mol% to about 5 mol% Na2O, 0 mol% to about 4 mol% K2O, 0 mol% to about 2 mol% ZrO2, 0 mol% to about 7 mol% P2O5, 0 mol% to about 0.3 mol% Fe2O3, 0 mol% to about 2 mol% MnO, and / or a combination of these. x % to about 0.2 mol% SnO2. In one or more embodiments, the composition may include 67 mol% to about 74 mol% SiO2, 11 mol% to about 15 mol% Al2O3, 5.5 mol% to about 9 mol% Li2O, 0.5 mol% to about 2 mol% ZnO, 2 mol% to about 4.5 mol% MgO, 3 mol% to about 4.5 mol% TiO2, 0 mol% to about 2.2 mol% B2O3, 0 mol% to about 1 mol% Na2O, 0 mol% to about 1 mol% K2O, 0 mol% to about 1 mol% ZrO2, 0 mol% to about 4 mol% P2O5, 0 mol% to about 0.1 mol% Fe2O3, 0 mol% to about 1.5 mol% MnO. x% to about 0.16 mol% SnO2. In one or more embodiments, the composition may include 70 mol% to 75 mol% SiO2, 10 mol% to about 15 mol% Al2O3, 5 mol% to about 13 mol% Li2O, 0 mol% to about 4 mol% ZnO, 0.1 mol% to about 8 mol% MgO, 0 mol% to about 5 mol% TiO2, 0.1 mol% to about 4 mol% B2O3, 0.1 mol% to about 5 mol% Na2O, 0 mol% to about 4 mol% K2O, 0 mol% to about 2 mol% ZrO2, 0 mol% to about 7 mol% P2O5, 0 mol% to about 0.3 mol% Fe2O3, 0 mol% to about 2 mol% MnO. x %, and 0.05 mol % to about 0.2 mol % SnO2.

[0124] In one or more embodiments, the composition comprises 52 mol% to about 63 mol% SiO2, 11 mol% to about 15 mol% Al2O3, 5.5 mol% to about 9 mol% Li2O, 0.5 mol% to about 2 mol% ZnO, 2 mol% to about 4.5 mol% MgO, 3 mol% to about 4.5 mol% TiO2, 0 mol% to about 2.2 mol% B2O3, 0 mol% to about 1 mol% Na2O, 0 mol% to about 1 mol% K2O, 0 mol% to about 1 mol% ZrO2, 0 mol% to about 4 mol% P2O5, 0 mol% to about 0.1 mol% Fe2O3, 0 mol% to about 1.5 mol% MnO, x %, and 0.08 mol % to about 0.16 mol % SnO2.

[0125] Other exemplary compositions of glass-based articles, prior to being chemically strengthened, as described herein, are shown in Table 1.

[0126] [Table 1-1]

[0127] [Table 1-2]

[0128] When the glass-based article comprises a glass-ceramic, the crystalline phases may include beta-spodumene, rutile, gahnite or other known crystalline phases and combinations thereof.

[0129] The glass-based article may be substantially planar, although other embodiments may use curved or otherwise shaped or shaped substrates. In some cases, the glass-based article may have a 3D or 2.5D shape. The glass-based article may be substantially optically clear, transparent, and free of light scattering. The glass-based article may have a refractive index ranging from about 1.45 to about 1.55. As used herein, refractive index values ​​refer to a wavelength of 550 nm.

[0130] Additionally or alternatively, the thickness of the glass-based article may be constant along one or more dimensions, or may vary along one or more of its dimensions for aesthetic and / or functional reasons. For example, the edges of the glass-based article may be thicker than the more central regions of the glass composition. The length, width and thickness dimensions of the glass-based article may also vary according to the application or use of the article.

[0131] The glass-based article may be characterized by the manner in which it is formed. For example, a glass-based article may be characterized as float formable (i.e., formed by a float process), downdrawable, and especially fusion formable or slot drawable (i.e., formed by a downdraw process such as a fusion draw process or a slot draw process).

[0132] Float-formable glass-based articles may be characterized by a smooth surface and uniform thickness, and are produced by floating molten glass on a bed of molten metal, typically tin. In an exemplary process, molten glass fed to the surface of the molten tin bed forms a floating glass ribbon. As this glass ribbon flows along the tin bath, its temperature gradually decreases until the glass ribbon solidifies into a solid glass-based article that is lifted from the tin onto rollers. Once away from the bath, the glass-based article can be further cooled and annealed to reduce internal stresses. If the glass-based article is a glass-ceramic, the glass-based article formed by the float process may be subjected to a ceramming process, whereby one or more crystalline phases are produced.

[0133] The down-draw process produces glass-based articles of uniform thickness with relatively pristine surfaces. The average bending strength of a glass-based article is controlled by the amount and size of surface flaws, so pristine surfaces with minimal contact have higher initial strength. If this high-strength glass-based article is then further strengthened (e.g., chemically), the resulting strength can be higher than that of a glass-based article with a lapped and polished surface. Down-drawn glass-based articles may be drawn to thicknesses of less than about 2 mm. Moreover, down-drawn glass-based articles have very flat and smooth surfaces that can be used in end applications without costly grinding and polishing. If the glass-based article is a glass-ceramic, the glass-based article formed by the down-draw process may be subjected to a ceramization process, whereby one or more crystalline phases are produced.

[0134] The fusion draw process employs, for example, a drawing tank having a passageway for receiving molten glass raw material. The passageway has weirs open at the top along the length of the passageway on either side of the passageway. When the passageway is filled with molten material, the molten glass spills over the weirs. The molten glass flows down the exterior surface of the drawing tank as two flowing glass films due to gravity. These exterior surfaces of the drawing tank extend downward and inward to meet at the lower edge of the drawing tank. The two flowing glass films meet at this edge and fuse to form a single flowing glass-based article. The fusion draw process offers the advantage that the exterior surface of the resulting glass-based article does not come into contact with any part of the apparatus because the two glass films flowing over the passageway fuse together. Thus, the surface properties of the glass-based article formed by the fusion draw process are not affected by such contact. If the glass-based article is a glass-ceramic, the glass-based article formed by the fusion process may be subjected to a ceramming process whereby one or more crystalline phases are produced.

[0135] The slot draw process differs from the fusion draw process. In the slot draw process, molten raw glass is provided to a drawing tank. The bottom of the drawing tank has an open slot with a nozzle extending the length of the slot. The molten glass flows through the slot / nozzle and is drawn downward as a continuous glass-based article to an annealing area. If the glass-based article is a glass-ceramic, the glass-based article formed by the slot draw process may be subjected to a ceramming process whereby one or more crystalline phases are produced.

[0136] In some embodiments, the glass-based article may be formed using thin rolling processes, such as those described in U.S. Pat. No. 8,713,972, entitled "Precision Glass Roll Forming Process and Apparatus," U.S. Pat. No. 9,003,835, entitled "Precision Roll Forming of Textured Sheet Glass," U.S. Patent Application Publication No. 2015 / 0027169, entitled "Methods And Apparatus For Forming A Glass Ribbon," and U.S. Patent Application Publication No. 2005 / 0099618, entitled "Apparatus and Method for Forming Thin Glass Articles," the contents of which are incorporated herein by reference in their entireties. More specifically, the glass-based article is formed by providing a vertical stream of molten glass, forming the provided stream of molten glass or glass ceramic with a pair of forming rolls maintained at a surface temperature of about 500° C. or greater, or about 600° C. or greater, to form a formed glass ribbon having a formed thickness, and sizing the formed glass ribbon with a pair of sizing rolls maintained at a surface temperature of about 400° C. or less to produce a sized glass ribbon having a desired thickness less than the formed thickness and a desired thickness uniformity.The apparatus used to form the glass ribbon may include a glass delivery apparatus for providing a supply stream of molten glass; a pair of forming rolls maintained at a surface temperature of about 500° C. or greater, spaced closely adjacent to one another defining a glass forming gap between the forming rolls, the glass forming gap being positioned vertically below the glass delivery apparatus for receiving the supply stream of molten glass and thinning the supply stream of molten glass between the forming rolls to form a formed glass ribbon having a formed thickness; and a pair of sizing rolls maintained at a surface temperature of about 400° C. or less, spaced closely adjacent to one another defining a glass sizing gap between the sizing rolls, the glass sizing gap being positioned vertically below the forming rolls for receiving the formed glass ribbon and thinning the formed glass ribbon to produce a sized gapped glass ribbon having a desired thickness and a desired thickness uniformity.

[0137] In some cases, thin-rolling techniques may be utilized when the viscosity of the glass precludes the use of fusion or slot-draw techniques, for example, thin-rolling techniques can be utilized to form glass-based articles when the glass exhibits a liquidus viscosity of less than 100 kP.

[0138] The glass-based article may be acid polished or otherwise treated to eliminate or reduce the effects of surface scratches.

[0139] Another aspect of the present disclosure relates to a method of forming a fracture-resistant glass-based article, comprising providing a glass-based substrate having a first surface and a second surface defining a thickness of about 1 millimeter or less, and inducing a stress profile in the glass-based substrate as described herein to provide a fracture-resistant glass-based article. In one or more embodiments, inducing the stress profile includes ion-exchanging a plurality of alkali ions into the glass-based substrate to form a non-zero alkali metal oxide concentration that varies along a substantial portion of the thickness (as described herein) or along the entire thickness. In one example, inducing the stress profile includes ion-exchanging a plurality of alkali ions into the glass-based substrate having a temperature of about 350° C. or greater (e.g., from about 350° C. to about 500° C.). + , K + , Rb + , Cs + or a combination thereof. In one example, the molten salt bath may include NaNO3 and have a temperature of about 485° C. In another example, the bath may include NaNO3 and have a temperature of about 430° C. The glass-based substrate may be immersed in the bath for about 2 hours or more, up to about 48 hours (e.g., about 12 hours to about 48 hours, about 12 hours to about 32 hours, about 16 hours to about 32 hours, about 16 hours to about 24 hours, or about 24 hours to about 32 hours).

[0140] In some embodiments, the method may include chemically strengthening or ion exchanging a glass-based substrate in multiple steps using successive immersion steps in multiple baths. For example, two or more baths may be used in sequence. The compositions of the two or more baths may include a single metal (e.g., Ag) in the same bath. + , Na + , K + , Rb + , or Cs +) or a combination of metals. When multiple baths are used, the baths may have the same or different compositions and / or temperatures from one another. The immersion time in each such bath may be the same or different to impart the desired stress profile.

[0141] In one or more embodiments, a second or subsequent bath may be utilized to produce a larger surface CS. In some cases, the method includes immersing the glass-based substrate in the second or subsequent bath to produce a larger surface CS without significantly affecting the chemical depth and / or DOC of the layer. In such embodiments, the second or subsequent bath may include a single metal (e.g., KNO3 or NaNO3) or a mixture of metals (KNO3 and NaNO3). The temperature of the second or subsequent bath may be adjusted to produce the larger surface CS. In some embodiments, the immersion time of the glass-based substrate in the second or subsequent bath may also be adjusted to produce a larger surface CS without affecting the chemical depth and / or DOC of the layer. For example, the immersion time in the second or subsequent bath may be less than 10 hours (e.g., about 8 hours or less, about 5 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, about 15 minutes or less, or about 10 minutes or less).

[0142] In one or more alternative embodiments, the method may include one or more heat treatment steps that may be used in combination with the ion exchange steps described herein. The heat treatment step includes heat treating the glass-based article to obtain a desired stress profile. In some embodiments, the heat treatment step includes annealing, heat strengthening, or heating the glass-based substrate to a temperature ranging from about 300° C. to about 600° C. The heat treatment may last from 1 minute to about 18 hours. In some embodiments, the heat treatment may be used after or during one or more ion exchange steps. EXAMPLES

[0143] The various embodiments are further clarified by the following examples, in which the examples are referred to as "substrates" before tempering, and are referred to as "articles" or "glass-based articles" after tempering has been applied.

[0144] Example 1 Glass-ceramic substrates were provided having the nominal compositions shown in Table 2 below. The glass-ceramic substrates were 0.8 mm thick and contained a crystalline phase assemblage including a β-spodumene solid solution as a predominant crystalline phase and one or more minor phases including rutile. The glass-ceramic substrates were immersed in a molten salt bath including NaNO3 having a temperature of 485° C. for 10 hours (Condition A), 13 hours (Condition B), or 24 hours (Condition C), or in a molten salt bath including NaNO3 having a temperature of 430° C. for 2 hours (Comparative Condition D) to form glass-ceramic articles.

[0145] [Table 2]

[0146] The stress profile of the glass-ceramic article was measured by microprobe and is shown in FIG. 5. As shown in FIG. 5, Na + Ions are exchanged through nearly the entire thickness of the article when a higher temperature bath is utilized (i.e., conditions A-C). In such glass-ceramics, Na2O is present in the CT region in an amount of about 1.2 mol % or greater. The glass-ceramic article ion-exchanged in the lower temperature bath (comparative condition D) exhibited a stress profile similar to known stress profiles.

[0147] Example 2 Glass substrates having the same composition as shown in Table 2 and a thickness of 0.8 mm, but with an amorphous structure (no crystalline phase), were chemically strengthened by immersion in a molten salt bath containing 100% NaNO3 having a temperature of about 430°C for various periods of time to provide glass articles. The DOC and maximum CT of the glass articles were measured using a scattered light polariscope (SCALP). As shown in Figure 6, the DOC and maximum CT increase with increasing length of immersion or ion exchange. The maximum CT value was observed after immersing the glass for about 16 hours.

[0148] The stress profile of the glass article of Example 2 was measured using SCALP. The stress profile is shown in FIG. 7. The upper part of the x-axis showing positive stress values ​​is the CT layer, and the lower part of the x-axis showing negative stress values ​​is the CS value. The stress profile of the glass article chemically strengthened for 16 hours showed a maximum CT value (i.e., 175 MPa) and a parabolic shape in the depth direction of 100 micrometers with substantially no linear portion. The surface CS measured by SCALP was about 410 MPa. Thus, the ratio of maximum CT to surface CS of Example 2 is about 0.4375.

[0149] Example 3 For comparison, the glass-ceramic substrate of Example 1 and the glass substrate of Example 2, each having a thickness of about 0.8 mm, were chemically strengthened by immersion in a molten salt bath of NaNO3 having a temperature of 350°C for 3.5 hours (Examples 3A and 3B, respectively). The resulting stress profiles of the glass-ceramic and glass articles shown in Figure 8 resemble an error function (erfc) or quasi-linear shape. Furthermore, the CS depth of the layer is smaller than the depth of the alkali ions exchanged into the glass or glass ceramic (or the chemical ion exchange depth).

[0150] When the glass-ceramic substrate of Example 1 and the glass substrate of Example 2, each having a thickness of about 0.8 mm, were subjected to chemical strengthening as described herein by immersion in a molten salt bath of NaNO3 having a temperature of 430°C for 24 hours (Examples 3C and 3D, respectively), the resulting glass-based articles exhibited a metal oxide concentration profile (obtained by EPMA) as shown in Figure 9. The metal oxide concentration profile was parabolic, with Na throughout the entire thickness. + The ion exchange of ions is shown. The chemical profile was measured using EMPA. The chemical depth of Na2O diffusion is shown to be greater than 400 micrometers. Furthermore, Na2O is present in a concentration of about 1 mole % or greater throughout the thickness, including the CT layer. The resulting glass-ceramic article of Example 3D exhibited excellent fracture resistance in a drop test in which the glass-ceramic substrate was mounted in the housing of an identical mobile phone. Specifically, five samples of Example 3D were assembled into a mobile phone device and dropped onto abrasive paper for successive drops starting at a depth of 50 cm. As each sample survived a drop from a height, the sample was dropped again from an increasing height until a crack occurred. At the time of cracking, the breakage height of the sample was recorded in FIG. 9A. Example 3D exhibited an average breakage height of 172.5 cm.

[0151] Figure 10 shows stress profiles of glass-based substrates chemically strengthened by known processes and according to the methods described herein. As shown in Figure 10, the stress profile of the glass-based article of the embodiments described herein has a shape that is substantially free of linear segments (having a length or absolute depth greater than about 50 micrometers) and exhibits a DOC of about 0.2·t, while the known stress profile exhibits a substantially linear portion from about 0.1 millimeters to a depth of about 0.7 millimeters (total length of about 0.6 millimeters or 600 micrometers). The known stress profile also exhibits a lower CT value and a smaller DOC.

[0152] Example 4 Glass substrates with the compositions in Table 2 (each with a thickness of about 1 mm) were chemically strengthened by immersion in a first molten salt bath of NaNO3 with a temperature of 430°C for 24 hours. One glass-based article was not subjected to any additional strengthening step (Example 4A). Three glass-based articles were subjected to a second strengthening step by immersion in a second molten salt bath of KNO3 with a temperature of 430°C for either 0.75 hours, 4 hours, or 8 hours (Examples 4B, 4C, and 4D, respectively). The stress profiles measured by SCALP of the resulting glass-based articles are shown in Figure 11. The depth or thickness of the glass-based article is plotted on the x-axis and the stress is plotted on the y-axis. The positive stress values ​​are the CT values ​​and the negative stress values ​​are the CS values. The spatial resolution of the instrument prevents the measurement of the CS associated with the second KNO3 ion exchange step. The glass-based articles of Examples 4A and 4B showed similar profiles. The glass-based articles of Examples 4C and 4D exhibited a decreased CT (compared to Examples 4A and 4B) and a decreased CS (compared to Examples 4A and 4B) over time after immersion in the second tempering step. The glass-based articles of Examples 4C and 4D also exhibited an increased DOC (compared to Examples 4A and 4B), such DOC values ​​being greater than 0.2·t.

[0153] FIG. 12 shows the J / m 2 The stored tensile energy in m / s is shown to vary from 15 J / m depending on the time of immersion in the second molten salt bath of KNO3. 2 The stored tensile energy can be calculated from the measured SCALP stress profile data using equation (3) above.

[0154] Figures 13 and 14 show the concentration profiles of each of KO and NaO as a function of depth (micrometers) for each of Examples 4B-4D. As shown in Figure 13, the chemical depth of KO is 3 micrometers (Example 4B, 0.75 hour immersion in KNO bath), 6 micrometers (Example 4C, 4 hour immersion in KNO bath), and 5 micrometers (Example 4D, 8 hour immersion in KNO bath). As shown in Figure 14, NaO penetrates the entire depth and has a concentration of about 1 mol% or more for each of Examples 4B-4D along the entire depth of the glass-based article.

[0155] Examples 4E and 4F included glass substrates (each having a thickness of about 1 mm) having the compositions in Table 2. The substrates were chemically strengthened by immersion in a first molten salt bath of NaNO3 having a temperature of 430°C for 24 hours, and heat treated in air to a temperature of 430°C for 4 hours or 8.25 hours, respectively. The stress profiles of the glass-based articles of Examples 4E and 4F are shown in Figure 15, with the stress profiles for Examples 4A, 4C and 4D shown for comparison. Figure 16 shows the same graph as Figure 15, but on a smaller scale to show the difference in the stress profiles at or near a depth of 0.5·t.

[0156] Example 5 Glass substrates (each having a thickness of about 1 mm) with the compositions in Table 2 were chemically strengthened by immersion in a first molten salt bath of NaNO3 having a temperature of 430°C for 24 hours. One glass-based article was not subjected to any additional strengthening step (Example 5A). Two glass-based articles were subjected to a second strengthening step by placing the glass-based articles in a furnace at 390°C and maintaining the glass-based articles in the furnace for 8 hours or 28 hours (Examples 5B-5C, respectively). Four glass-based articles were subjected to a third strengthening step (after either the first strengthening step and a different second strengthening step) by immersion in a second molten salt bath of KNO3 having a temperature of 430°C for 4 hours or 8 hours (Examples 5D-5G). The strengthening steps for each of Examples 5A-5G are shown in Table 3. The measured CT values ​​are also shown in Table 3.

[0157] [Table 3]

[0158] The resulting stress profile of the glass-based article is shown in Figure 17. The depth or thickness of the glass-based article is plotted on the x-axis and the stress is plotted on the y-axis. Positive stress values ​​are CT values ​​and negative stress values ​​are CS values. As shown in Figure 17, as the duration of the second and / or third heat treatments increased, the DOC increased and the CT decreased. The decrease in DOC and CT is more clearly shown in Figures 18 and 19, respectively.

[0159] The glass-based articles of Examples 5A-5G were then subjected to a poke test in which tape was applied to one side of the glass-based article and a sharp instrument was struck against the opposite bare side to break it. The number of fragments obtained can be correlated to the stored tensile energy of the glass-based article. Examples 5A, 5B, and 5D exhibited a large number of fragments (i.e., more than 50 and even 100), while Example 5F exhibited 10 fragments, Example 5C exhibited 3 fragments, and Examples 5E and 5G exhibited 4 fragments. Examples 5A, 5B, and 5D, which exhibited a large number of fragments, exhibited higher CT (greater than about 100 MPa) than Examples 5C, 5E, 5F, and 5G, which all had CT values ​​of about 100 MPa or less.

[0160] Example 6 Glass substrates with a nominal composition of 57.5 mol% SiO2, 16.5 mol% Al2O3, 16.7 mol% Na2O, 2.5 mol% MgO, and 6.5 mol% P2O5 and thicknesses of approximately 0.4 mm, 0.55 mm, or 1 mm were chemically strengthened. The thicknesses and chemical strengthening conditions are shown in Table 4.

[0161] [Table 4]

[0162] Example 6A was immersed in a molten salt bath as shown in Table 4 for 4, 8, 16, 32, 64, and 128 hours (Examples 6A-1 to 6A-6). Example 6B was immersed in a molten salt bath as shown in Table 4 for 4, 8, 16, 32, 64, and 128 hours (Examples 6B-1 to 6B-6). Example 6C was immersed in a molten salt bath as shown in Table 4 for 1, 2, 4, 8, 16, and 32 hours (Examples 6C-1 to 6C-6). Example 6D was immersed in a molten salt bath as shown in Table 4 for 4, 8, 16, 32, 64, and 128 hours (Examples 6D-1 to 6D-6). The stress profiles of Examples 6A-1 through 6A-6, 6B-1 through 6B-6, 6C-1 through 6C-6, and 6D-1 through 6D-6 are shown in Figures 20, 22, 24, and 26, respectively. In Figures 20, 22, 24, and 26, the depth or thickness of the glass article is plotted on the x-axis and stress is plotted on the y-axis. Positive stress values ​​are CT values ​​and negative stress values ​​are CS values.

[0163] The CT and DOC values ​​as a function of time of immersion in the molten salt bath for Examples 6A-1 to 6A-6, Examples 6B-1 to 6B-6, Examples 6C-1 to 6C-6, and Examples 6D-1 to 6D-6 are shown in Figures 21, 23, 25, and 27, respectively.

[0164] Example 7 Glass substrates having a nominal composition as shown in Table 2 and a thickness of about 1 mm were subjected to chemical strengthening in a molten salt bath containing 100% NaNO3 at a temperature of 430° C. The duration of immersion of the glass substrate in the molten salt bath is shown in Table 5.

[0165] [Table 5]

[0166] The stress profiles of the glass-based articles of Examples 7A-7G are shown in Figure 28. These stress profiles were measured using SCALP. As shown in Figure 28, immersion of the glass substrates in a molten salt bath for 16 and 24 hours results in glass-based articles that exhibit maximum surface CS and CT values ​​in absolute terms. Graphs showing the change in CT value and stored tensile energy, both as a function of ion-exchange time, are shown in Figure 29.

[0167] Example 8 Glass substrates having nominal compositions as shown in Table 2 and each having a thickness of about 0.8 mm were chemically strengthened in a molten salt bath containing a mixture of NaNO3 and NaSO4 at a temperature of 500°C for 15 minutes (Comparative Example 8A) and 16 hours (Example 8B). The stress profiles of the glass-based articles of Examples 8A and 8B are shown in Figure 30. As shown in Figure 30, Comparative Example 8A exhibited a known stress profile, whereas Example 8B exhibited a stress profile according to one or more of the present disclosures. The stored tensile energy of the glass-based articles of Examples 8A and 8B was calculated in the same manner as Examples 4B-4D. The calculated stored tensile energy is plotted as a function of measured CT (MPa), as shown in Figure 31.

[0168] As shown in FIG. 31, Comparative Example 8A exhibited a much higher stored tensile energy value for a given CT value than Example 8B (for the same CT value). Specifically, at a CT of about 55 MPa, Comparative Example 8A exhibited a stored tensile energy value of about 8 J / m 2 The stored tensile energy of the example was about 3.5 J / m 2 8B. Comparative Example 8A and Example 8B fractured, with Example 8B fractured into fewer pieces than Comparative Example 8A. Comparative Example 8A fractured into a much larger number of pieces. Thus, without being bound by theory, it is believed that controlling the stored tensile energy would provide a way to control or predict the fracture pattern or number of pieces resulting from the fracture.

[0169] Glass substrates having nominal compositions as shown in Table 2 and each having a thickness of about 1 mm were chemically strengthened in a molten salt bath containing NaNO3 at a temperature of 430°C for 4 hours (Comparative Example 8C) and 61.5 hours (Example 8D). Comparative Example 8C exhibited a known stress profile, whereas Example 8D exhibited a stress profile according to one or more of the present disclosures. The stored tensile energy of Examples 8C and 8D was calculated using the same method used for Examples 4B-4D and plotted as a function of measured CT (MPa) as shown in Figure 32.

[0170] As shown in Figure 32, Comparative Example 8C exhibited a much higher stored tensile energy value for a given CT value than Example 8D (for the same CT value). Comparative Example 8C and Example 8D cracked, with Example 8D cracking into fewer pieces than Comparative Example 8C. Comparative Example 8C cracked into a much higher number of pieces.

[0171] Example 9 A glass substrate having a nominal composition of 70.9 mol% SiO2, 12.8 mol% Al2O3, 1.95 mol% B2O3, 7.95 mol% Li2O, 2.43 mol% Na2O, 2.98 mol% MgO, 0.89 mol% ZnO, and 0.1 mol% SnO2 and a thickness of about 0.8 mm was subjected to the ion exchange conditions of Table 6. Various properties of Example 9 are compared to Example 2 in Table 7.

[0172] [Table 6]

[0173] [Table 7]

[0174] The stress profiles were measured for the glass-based articles of Example 9. These stress profiles exhibited the shapes described herein.

[0175] Glass substrates according to Examples 2, 6, and Comparative Example 9A were provided having the same thickness as Example 9. The glass substrate according to Example 2 was ion-exchanged in a molten bath of 100% NaNO3 having a temperature of 430°C for 33 hours. The glass substrate according to Example 6 was ion-exchanged and exhibited the known error function stress profile. Comparative Example 9A was ion-exchanged in a molten bath of 100% NaNO3 having a temperature of 390°C for 16 hours and also exhibited the known error function stress profile. As used herein, the term "error function stress profile" refers to a stress profile similar to that of FIG. 1.

[0176] The glass-based articles from Example 2, Example 6, Example 9, and Comparative Example 9A were then mounted on the same mobile phone device. The phone devices were dropped from incremental heights starting at 20 centimeters onto 30-grit abrasive paper. If the glass-based article survived the drop from a certain height (e.g., 20 cm), the mobile phone was dropped again from a higher height (e.g., 30 cm, 40 cm, 50 cm, etc.). The heights at which the glass-based articles broke are plotted in FIG. 33, which also shows the average breakage heights for the samples of Examples 2, 6, and 9, as well as Comparative Example 9A. As shown in FIG. 33, Examples 2 and 9 broke at significantly higher drop heights than Example 6 and Comparative Example 9A. Specifically, Example 6 and Comparative Example 9A broke at drop heights of about 38 cm and 55 cm, respectively, while Examples 2 and 9 broke at drop heights of about 147 cm and 132 cm, respectively.

[0177] The same test was repeated on new samples using the same cell phone device on 180 grit sandpaper. The average break height for Example 6 was 190 cm, for Comparative Example 9A it was 204 cm, for Example 2 it was 214 cm, and for Example 9 it was 214 cm.

[0178] Ion-exchanged glass substrates according to Comparative Example 9B, having a nominal composition of 65 mol% SiO2, 5 mol% B2O3, 14 mol% Al2O3, 14 mol% Na2O, 2 mol% MgO, and 0.1 mol% SnO2, and a thickness of 0.8 mm, exhibited known error function stress profiles. Samples of the glass-based articles of Examples 2 and 6 (which exhibit the stress profiles described above in this example), Comparative Example 9B, and the glass-based article of Example 9 ion-exchanged according to Condition 4 as shown in Table 5, were subjected to A-ROR testing as described herein.

[0179] Examples 6 and 9, as well as Comparative Example 9B, were polished using loads or pressures of 25 psi (about 172 kPa) and 45 psi (about 310 kPa), and Example 2 was polished using only a load of 25 psi (about 172 kPa). The AROR data is shown in Figure 34. As shown in Figure 34, Examples 2 and 9 exhibited higher failure loads than Example 6 and Comparative Example 9B.

[0180] Samples of the glass-based articles of Examples 2 (ion-exchanged as described above in this Example) and 9 (ion-exchanged according to Condition 4) were subjected to four-point bend testing, the results of which are shown in the Weibull distribution plot of Figure 35. As shown in Figure 35, Example 9 exhibited a higher failure load or stress (e.g., greater than about 400 MPa).

[0181] As noted above, glass-based articles made from compositions having strain points greater than 525° C. allow for ion exchange temperatures (or ion exchange bath temperatures) ranging from about 350° C. to about 480° C. In some embodiments, glass compositions exhibiting a diffusivity greater than about 800 square millimeters per hour allow metal oxides to diffuse into the glass-based article and penetrate the entire depth or thickness of the article so rapidly that stress relaxation is minimized. Excessive stress relaxation can reduce the surface compressive stress of the glass-based article.

[0182] It will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the spirit or scope of the present invention.

[0183] Preferred embodiments of the present invention will be described below in detail.

[0184] EMBODIMENT 1 In glass-based articles, a first surface and a second surface opposite the first surface, the second surface defining a thickness (t); a concentration of metal oxide that is non-zero and varies along a thickness range from about 0·t to about 0.3·t; having If the glass-based article breaks, the glass-based article will break into pieces of 1 square inch (approximately 6.4516 cm 2 ) glass-based articles that break into at least 2 pieces per impact.

[0185] EMBODIMENT 2 2. The glass-based article of embodiment 1, wherein the concentration of the metal oxide is non-zero and varies along the entire thickness.

[0186] EMBODIMENT 3 3. The glass-based article of claim 1 or 2, wherein the metal oxide creates a stress along the thickness range.

[0187] EMBODIMENT 4 4. The glass-based article of any one of claims 1 to 3, wherein a concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface and increases from that point to the second surface.

[0188] EMBODIMENT 5 5. The glass-based article of any one of claims 1 to 4, further having a surface compressive stress (CS) of about 300 MPa or more.

[0189] EMBODIMENT 6 6. The glass-based article of embodiment 5, wherein the surface CS is about 600 MPa or greater.

[0190] EMBODIMENT 7 7. The glass-based article of any one of claims 1 to 6, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol% throughout the thickness.

[0191] EMBODIMENT 8 8. The glass-based article of any one of claims 1 to 7, wherein a concentration of the metal oxide at the first surface is about 1.5 times greater than a concentration of the metal oxide at a depth equal to about 0.5·t.

[0192] EMBODIMENT 9 9. The glass-based article of any one of claims 1 to 8, wherein the glass-based article has a total concentration of the metal oxides ranging from about 1 mol% to about 15 mol%.

[0193] EMBODIMENT 10 10. The glass-based article of any one of the preceding claims, wherein the metal oxide comprises any one or more of Li2O, Na2O, KO, Rb2O, and Cs2O.

[0194] EMBODIMENT 11 11. The glass-based article of any one of the preceding claims, further having a surface C S of about 300 MPa or more and a chemical depth of layer of about 0.4·t or more.

[0195] EMBODIMENT 12 12. The glass-based article of any one of the preceding claims, further comprising a CS layer extending from the first surface to a DOC that is about 0.1·t or greater.

[0196] EMBODIMENT 13 13. The glass-based article of any one of the preceding claims, further comprising a central tension (CT) region, the CT region having a concentration gradient of said metal oxide.

[0197] EMBODIMENT 14 14. The glass-based article of claim 13, wherein the CT region has a maximum CT, and a ratio of maximum CT to surface CS ranges from about 0.01 to about 0.5.

[0198] EMBODIMENT 15 15. The glass-based article of any one of the preceding claims, wherein t comprises about 3 millimeters or less.

[0199] EMBODIMENT 16 16. The glass-based article of any one of the preceding claims, wherein t comprises about 1 millimeter or less.

[0200] EMBODIMENT 17 17. The glass-based article of any one of the preceding claims, further having an amorphous structure.

[0201] EMBODIMENT 18 18. The glass-based article of any one of the preceding claims, further having a crystalline structure.

[0202] EMBODIMENT 19 19. The glass-based article of any one of the preceding claims, further exhibiting a transmittance of about 88% or greater over a wavelength range from about 380 nm to about 780 nm.

[0203] EMBODIMENT 20 20. The glass-based article of any one of the preceding claims, further exhibiting a transmittance of about 10% or less over a wavelength range from about 380 nm to about 780 nm.

[0204] EMBODIMENT 21 Under CIE illuminant F02, the LED is approximately 88 or higher * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 * 21. The glass-based article of any one of the preceding claims, further showing CIELAB color space coordinates of:

[0205] EMBODIMENT 22 Under CIE illuminant F02, the L * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 * 22. The glass-based article of any one of the preceding claims, further showing CIELAB color space coordinates of:

[0206] EMBODIMENT 23 a first surface and a second surface opposite the first surface, a first metal oxide concentration, and a second metal oxide concentration, the first surface and the second metal oxide concentration defining a thickness (t); and the first metal oxide concentration is in the range of about 0 mol % to about 15 mol % along a first thickness range of about 0·t to about 0.5·t; 23. The glass-based article of any one of the preceding claims, wherein the second metal oxide concentration is in the range of about 0 mol% to about 10 mol% along a second thickness range of about 0 micrometers to about 25 micrometers.

[0207] EMBODIMENT 24 24. The glass-based article of embodiment 23, further comprising a third metal oxide.

[0208] EMBODIMENT 25 In glass-based articles, a first surface and a second surface opposite the first surface, the first surface defining a thickness (t) of less than about 3 millimeters; and a stress profile extending through the thickness; having all points of the stress profile between thickness ranges of about 0·t to 0.3·t and greater than 0.7·t have a tangent less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer; the stress profile has a maximum CS, a DOC, and a maximum CT, the ratio of maximum CT to maximum CS being in the range of about 0.01 to about 0.5, and the DOC being greater than or equal to about 0.1 t; If the glass-based article breaks, the glass-based article will break into pieces of 1 square inch (approximately 6.4516 cm 2 ) glass-based articles that break into at least 2 pieces per impact.

[0209] EMBODIMENT 26 26. The glass-based article of embodiment 25, further having a surface CS of about 300 MPa or greater.

[0210] EMBODIMENT 27 27. The glass-based article of claim 26, wherein the surface CS is about 600 MPa or greater.

[0211] EMBODIMENT 28 28. The glass-based article of any one of claims 25 to 27, further having a surface CS of about 300 MPa or more and a chemical depth of layer (DOL) of about 0.4·t or more.

[0212] EMBODIMENT 29 29. The glass-based article of any one of claims 25 to 28, further comprising a CS layer extending from the first surface to a DOC that is about 0.1·t or greater.

[0213] EMBODIMENT 30 30. The glass-based article of any one of embodiments 25 to 29, further comprising a CT region, the CT region comprising a concentration gradient of a metal oxide.

[0214] EMBODIMENT 31 31. The glass-based article of claim 30, wherein the CT region has a maximum CT, and a ratio of maximum CT to surface CS ranges from about 0.01 to about 0.5.

[0215] EMBODIMENT 32 32. The glass-based article of any one of embodiments 25 to 31, wherein t comprises about 2 millimeters or less.

[0216] EMBODIMENT 33 33. The glass-based article of any one of claims 25 to 32, wherein t comprises about 1 millimeter or less.

[0217] EMBODIMENT 34 In glass-based articles, a first surface and a second surface opposite the first surface, the first surface defining a thickness (t); a concentration of metal oxide that is non-zero and varies along a thickness range from about 0·t to about 0.3·t; and Surface CS of approximately 200 MPa or more, The glass-based article has

[0218] EMBODIMENT 35 35. The glass-based article of embodiment 34, wherein the thickness range is from about 0·t to about 0.4t.

[0219] EMBODIMENT 36 36. The glass-based article of claim 34 or 35, wherein the thickness range is from about 0·t to about 0.45t.

[0220] EMBODIMENT 37 37. The glass-based article of any one of claims 34 to 36, wherein the metal oxide creates a stress along the thickness range.

[0221] EMBODIMENT 38 38. The glass-based article of claim 37, wherein the metal oxide has the largest ionic diameter of all of the metal oxides in the glass-based article.

[0222] EMBODIMENT 39 39. The glass-based article of any one of claims 34 to 38, wherein a concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface and increases from that point to the second surface.

[0223] EMBODIMENT 40 If the glass-based article breaks, the glass-based article will break into pieces of 1 square inch (approximately 6.4516 cm 2 At least one chip per square inch 2 40. The glass-based article of any one of claims 34 to 39, wherein the glass-based article breaks into up to 40 pieces per 100 mm.

[0224] EMBODIMENT 41 The glass-based article has a thickness of about 450 μm at about 460° C. 2 / hr or more, a maximum CT, and a DOC greater than about 0.15·t, and wherein the surface CS is 1.5 times or more the maximum CT.

[0225] EMBODIMENT 42 The glass-based article has a viscosity of about 0.7 MPa m 1 / 2 Fracture toughness (K 1C 42. The glass-based article of any one of claims 34 to 41, wherein

[0226] EMBODIMENT 43 42. The glass-based article of claim 41, wherein the surface CS is greater than the maximum CT.

[0227] EMBODIMENT 44 44. The glass-based article of any one of claims 34 to 43, wherein the surface CS is about 300 MPa or greater.

[0228] EMBODIMENT 45 45. The glass-based article of any one of claims 34 to 44, wherein the surface CS is about 600 MPa or greater.

[0229] EMBODIMENT 46 46. ​​The glass-based article of any one of claims 34 to 45, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol% throughout the thickness.

[0230] EMBODIMENT 47 47. The glass-based article of any one of claims 34 to 46, wherein a concentration of the metal oxide at the first surface is about 1.5 times greater than a concentration of the metal oxide at a depth equal to about 0.5·t.

[0231] EMBODIMENT 48 48. The glass-based article of any one of claims 34 to 47, wherein the total concentration of metal oxides is in the range of about 1 mol% to about 15 mol%.

[0232] EMBODIMENT 49 49. The glass-based article of any one of claims 34 to 48, wherein the metal oxide comprises any one or more of Li2O, Na2O, KO, Rb2O, and Cs2O.

[0233] EMBODIMENT 50 50. The glass-based article of any one of embodiments 34 to 49, further having a chemical depth of layer of about 0.4·t or greater.

[0234] EMBODIMENT 51 51. The glass-based article of any one of claims 34 to 50, further comprising a CS layer extending from the first surface to a DOC that is about 0.1·t or greater.

[0235] EMBODIMENT 52 52. The glass-based article of any one of claims 34 to 51, further comprising a CT region, the CT region comprising a concentration gradient of said metal oxide.

[0236] EMBODIMENT 53 53. The glass-based article of claim 52, wherein the CT region has a maximum CT, and a ratio of maximum CT to surface CS ranges from about 0.01 to about 0.5.

[0237] EMBODIMENT 54 54. The glass-based article of any one of embodiments 34 to 53, wherein t comprises about 3 millimeters or less.

[0238] EMBODIMENT 55 55. The glass-based article of any one of embodiments 34 to 54, wherein t comprises about 1 millimeter or less.

[0239] EMBODIMENT 56 In glass-based articles, a first surface and a second surface opposite the first surface, the second surface defining a thickness (t); Metal oxides that form a concentration gradient, having a concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface and increases from that point to the second surface; the concentration of the metal oxide at the point is not zero, The glass-based article has a viscosity of about 0 J / m 2 Over 20J / m 2 1. A glass-based article exhibiting a stored tensile energy of less than 100 nm.

[0240] EMBODIMENT 57 57. The glass-based article of embodiment 56, further having a surface CS of about 300 MPa or greater.

[0241] EMBODIMENT 58 58. The glass-based article of claim 57, wherein the surface CS is about 600 MPa or greater.

[0242] EMBODIMENT 59 59. The glass-based article of any one of claims 56 to 58, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol% throughout the thickness.

[0243] EMBODIMENT 60 60. The glass-based article of any one of claims 56 to 59, wherein the concentration of the metal oxide at the first surface is about 1.5 times greater than the concentration of the metal oxide at a depth equal to about 0.5·t.

[0244] EMBODIMENT 61 61. The glass-based article of any one of claims 56 to 60, wherein the total concentration of metal oxides is in the range of about 1 mol% to about 15 mol%.

[0245] EMBODIMENT 62 62. The glass-based article of any one of claims 56 to 61, wherein the metal oxide comprises any one or more of Li2O, Na2O, KO, Rb2O, and Cs2O.

[0246] EMBODIMENT 63 63. The glass-based article of any one of embodiments 56 to 62, further having a surface C S of about 200 MPa or more and a chemical depth of layer of about 0.4·t or more.

[0247] EMBODIMENT 64 64. The glass-based article of any one of claims 56 to 63, further comprising a CS layer extending from the first surface to a DOC that is about 0.1·t or greater.

[0248] EMBODIMENT 65 65. The glass-based article of any one of claims 56 to 64, further comprising a CT region, the CT region comprising a concentration gradient of said metal oxide.

[0249] EMBODIMENT 66 66. The glass-based article of embodiment 65, wherein the CT region has a maximum CT, and a ratio of maximum CT to surface CS ranges from about 0.01 to about 0.5.

[0250] EMBODIMENT 67 67. The glass-based article of any one of embodiments 56 to 66, wherein t comprises about 3 millimeters or less.

[0251] EMBODIMENT 68 68. The glass-based article of any one of embodiments 56 to 67, wherein t comprises about 1 millimeter or less.

[0252] EMBODIMENT 69 In glass-based articles, a first surface and a second surface opposite the first surface, the first surface defining a thickness (t) of less than about 3 millimeters; and a stress profile extending through the thickness; having all points of the stress profile between thickness ranges of about 0·t to 0.3·t and greater than 0.7·t have a tangent less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer; the stress profile has a maximum CS, a DOC, and a maximum CT, the ratio of maximum CT to maximum CS being in the range of about 0.01 to about 0.5, and the DOC being greater than or equal to about 0.1 t; The glass-based article has a viscosity of about 0 J / m 2 Over 20J / m 2 1. A glass-based article exhibiting a stored tensile energy of less than 100 nm.

[0253] EMBODIMENT 70 70. The glass-based article of embodiment 69, further comprising a non-zero concentration of metal oxide that varies continuously along its thickness.

[0254] EMBODIMENT 71 71. The glass-based article of embodiment 69 or 70, further comprising a non-zero concentration of metal oxide that varies continuously along a thickness segment of less than about 10 micrometers.

[0255] EMBODIMENT 72 72. The glass-based article of any one of claims 69 to 71, wherein the maximum CS comprises about 300 MPa or greater.

[0256] EMBODIMENT 73 73. The glass-based article of any one of claims 69 to 72, wherein the maximum CS comprises about 600 MPa or greater.

[0257] EMBODIMENT 74 74. The glass-based article of any one of embodiments 69 to 73, further having a chemical depth of layer of about 0.4·t or greater.

[0258] EMBODIMENT 75 75. The glass-based article of any one of claims 69 to 74, further comprising a CT region, the CT region comprising a concentration gradient of said metal oxide.

[0259] EMBODIMENT 76 76. The glass-based article of any one of embodiments 69 to 75, wherein t comprises about 3 millimeters or less.

[0260] EMBODIMENT 77 77. The glass-based article of any one of embodiments 69 to 76, wherein t comprises about 1 millimeter or less.

[0261] EMBODIMENT 78 In glass-based articles, Stress profile including CS and CT regions, having The CT region has the formula:

[0262]

number

[0263] is defined by wherein MaxCT is the maximum CT value given as a positive value in units of MPa, x is the position along the thickness (t) in micrometers, and n is between 1.5 and 5.

[0264] EMBODIMENT 79 79. The glass-based article of embodiment 78, wherein the CT region has a maximum CT value in the range of about 50 MPa to about 250 MPa, and the maximum CT value is at a depth in the range of about 0.4t to about 0.6t.

[0265] EMBODIMENT 80 80. The glass-based article of claim 78 or 79, wherein the stress profile has a gradient in the range of about 20 MPa / micrometer to about 200 MPa / micrometer over a thickness in the range of about 0t to about 0.1t.

[0266] Embodiment 81 81. The glass-based article of any one of claims 78-80, wherein the stress profile is defined by a plurality of error functions, measured from 0.5t to the surface.

[0267] EMBODIMENT 82 1. A method of forming a fracture resistant glass-based article, comprising: providing a glass-based substrate having a first surface and a second surface defining a thickness of about 3 millimeters or less; generating a stress profile in the glass-based substrate having a CT layer and a CS layer, the CS layer having a surface CS, a chemical depth of about 0.4t or greater and a DOC of about 0.1·t or greater, the CT layer having a maximum CT, the ratio of maximum CT to surface CS being about 0.01 to about 0.5; The method comprising:

[0268] EMBODIMENT 83 83. The method of embodiment 82, wherein generating the stress profile comprises ion-exchanging a plurality of metal ions into the glass-based substrate to form a metal oxide concentration gradient comprising a non-zero concentration of metal oxide extending along the thickness.

[0269] EMBODIMENT 84 84. The method of embodiment 83, wherein the non-zero concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface and increases from that point to the second surface.

[0270] EMBODIMENT 85 85. The method of any one of claims 82 to 84, wherein the CT layer has a concentration gradient of the metal oxide.

[0271] EMBODIMENT 86 86. The method of any one of embodiments 82 to 85, further comprising increasing the surface CS to about 100 MPa or more after generating the stress profile.

[0272] EMBODIMENT 87 87. The method of embodiment 86, wherein generating the stress profile comprises performing a first ion-exchange of a first plurality of ions into the glass-based substrate to form a concentration gradient of the metal oxide including a non-zero concentration of the metal oxide extending along the thickness, and increasing the surface CS comprises performing a second ion-exchange of a second plurality of alkali ions into the glass-based substrate having the concentration gradient of the metal oxide.

[0273] EMBODIMENT 88 87. The method of embodiment 86, wherein generating the stress profile comprises performing a first ion exchange of a plurality of ions into the glass-based substrate to form a concentration gradient of the metal oxide including a non-zero concentration of the metal oxide extending along the thickness, the plurality of ions comprising two different ions having different ionic radii from each other.

[0274] EMBODIMENT 89 In the use of the glass composition in tempered glass, The glass composition comprises, in mole percent: SiO2 in an amount ranging from about 68 to about 75; Al2O3 in an amount ranging from about 12 to about 15; B2O3 in an amount ranging from about 0.5 to about 5; LiO in an amount ranging from about 2 to about 8; Na2O in an amount ranging from about 0 to about 6; MgO in an amount ranging from about 1 to about 4; ZnO in an amount ranging from about 0 to about 3; and CaO in an amount ranging from about 0 to about 5; Including, the glass substrate is ion-exchangeable and amorphous; The glass substrate is a ratio of Li2O to R2O ranging from about 0.5 to about 1; a difference between the total amount of R2O and the amount of Al2O3 ranging from about -5 to about 0; R in the range of about 0 to about 3 x the difference between the total amount of O (mol %) and the amount of Al2O3, and the ratio of the amount of MgO (mol %) to the total amount of RO (mol %) ranging from about 0 to about 2; Indicates one or more of the following: The glass substrate is substantially free of nucleating agents.

[0275] EMBODIMENT 90 In the glass substrate, expressed in mole percent: SiO2 in an amount ranging from about 68 to about 75; Al2O3 in an amount ranging from about 12 to about 15; B2O3 in an amount ranging from about 0.5 to about 5; LiO in an amount ranging from about 2 to about 8; Na2O in an amount ranging from about 0 to about 6; MgO in an amount ranging from about 1 to about 4; ZnO in an amount ranging from about 0 to about 3; and CaO in an amount ranging from about 0 to about 5; having a composition comprising the glass substrate is ion-exchangeable and amorphous; The glass substrate is a ratio of Li2O to R2O ranging from about 0.5 to about 1; a difference between the total amount of R2O and the amount of Al2O3 ranging from about -5 to about 0; R in the range of about 0 to about 3 x the difference between the total amount of O (mol %) and the amount of Al2O3, and the ratio of the amount of MgO (mol %) to the total amount of RO (mol %) ranging from about 0 to about 2; Indicates one or more of the following: A glass substrate, wherein the glass substrate is substantially free of nucleating agents.

[0276] EMBODIMENT 91 In the glass substrate, expressed in mole percent: SiO2 in an amount ranging from about 68 to about 75; Al2O3 in an amount ranging from about 12 to about 15; B2O3 in an amount ranging from about 0.5 to about 5; LiO in an amount ranging from about 2 to about 8; Na2O in an amount ranging from about 0 to about 6; MgO in an amount ranging from about 1 to about 4; ZnO in an amount ranging from about 0 to about 3; and CaO in an amount ranging from about 0 to about 5; having a composition comprising the glass substrate is amorphous and the glass is strengthened; The glass substrate having a varying concentration of Na2O and being substantially free of a nucleating agent.

[0277] EMBODIMENT 92 a ratio of Li2O to R2O ranging from about 0.5 to about 1; a difference between the total amount of R2O and the amount of Al2O3 ranging from about -5 to about 0; R in the range of about 0 to about 3 x the difference between the total amount of O (mol %) and the amount of Al2O3, and the ratio of the amount of MgO (mol %) to the total amount of RO (mol %) ranging from about 0 to about 2; 92. The strengthened glass substrate of embodiment 91, further comprising any one or more of:

[0278] EMBODIMENT 93 In the glass substrate, expressed in mole percent: SiO2 in an amount of 60 mol% to 72 mol%, AlO in an amount of 5 mol % to 20 mol %, MgO in an amount of 2 mol % to 4 mol %, Li2O in an amount of 6 mol% to 10 mol%, Na2O in an amount of 0 mol% to 10 mol%, an alkaline earth metal oxide in an amount of from greater than zero to less than 15 mol %, said alkaline earth metal oxide comprising CaO in an amount of from greater than zero to less than 2 mol %; B2O3 in an amount from 0 mol% to 4 mol%, K2O in an amount from zero to 2 mole percent; having a composition comprising the composition is substantially free of ZnO; The sum of Li2O+Na2O+K2O is 5 mol% to 18 mol%; A glass substrate, in which the ratio of Li2O to R2O is 0.5 to 1.0, and R2O is the sum of Li2O+Na2O+K2O.

[0279] EMBODIMENT 94 94. The glass substrate of embodiment 93, wherein the total amount of alkaline earth metals is from greater than zero to less than or equal to 14 mol %.

[0280] EMBODIMENT 95 94. The glass substrate of embodiment 93, wherein the total amount of alkaline earth metals is from greater than zero to less than or equal to 12 mol %.

[0281] EMBODIMENT 96 94. The glass substrate of embodiment 93, wherein the total amount of alkaline earth metals is from 2.5 mol % to 8 mol %.

[0282] EMBODIMENT 97 94. The glass substrate of embodiment 93, wherein the composition has P2O5 in an amount of 0 mol % to 10 mol %.

[0283] EMBODIMENT 98 94. The glass substrate of embodiment 93, wherein the composition comprises Fe2O3 in an amount less than 1 mol %.

[0284] EMBODIMENT 99 94. The glass substrate of embodiment 93, wherein the composition comprises Fe2O3 in an amount less than 0.1 mol %.

[0285] EMBODIMENT 100 94. The glass substrate of embodiment 93, wherein the composition comprises As2O3 in an amount less than 0.1001 mol %.

[0286] EMBODIMENT 101 94. The glass substrate of embodiment 93, wherein the concentration of Na2O is varied.

[0287] EMBODIMENT 102 94. The glass substrate of embodiment 93, wherein the glass substrate is ion-exchangeable and amorphous.

[0288] EMBODIMENT 103 94. The glass substrate of embodiment 93, wherein the glass substrate has a thickness of 0.4 millimeters to 3 millimeters and a maximum central tension of 100 MPa to 250 MPa. [Explanation of symbols]

[0289] 100 Glass-based products 101, 201, 302 First Surface 110, 210, 310 surface CS 120, 220, 320 maximum central tension (CT) 130, 230 Depth of Layer (DOL) 200 Chemically strengthened glass-based articles 300 Glass-based article of the embodiment 304 Second Surface 312, 340 Stress Profiles 315 CS layer 317 DOC 325 CT layer 342 Chemistry Depth 400 Ring-on-ring configuration when polishing 410 Polished glass-based articles 420 Support Ring 430 Load Ring 500 devices 510 Test Stand 512 Solid Base 514 Abrasive paper, sheets containing abrasive material 515 Sample Holder 516 void 518 Glass-based product samples 520 Adhesive Tape 530 steel ball

Claims

1. In the glass substrate, SiO in an amount ranging from 45 mol % to 75 mol % 2 , Al in an amount ranging from 5 mol% to 28 mol% 2 O 3 , Na in an amount ranging from 0.1 mol % to 14 mol % 2 O. Li in an amount ranging from 4 mol% to 10 mol% 2 O. P in an amount ranging from 0 mol% to 10 mol% 2 O 5 , B in an amount ranging from 0 mol% to 4 mol% 2 O 3 , and MgO in an amount less than 5 mol % Including, R x The total amount (mol%) of metal oxide represented by O and Al 2 O 3 between the amount (mol%) of x O-Al 2 O 3 ) ranges from 0 to 3, where R x O is Li in the glass substrate. 2 O, Na 2 O.K. 2 O, Rb 2 O, Cs 2 The total of O, MgO, BaO, CaO, and ZnO, The glass substrate contains ZnO in an amount of up to 2 mol %, is substantially free of CaO, and contains a nucleating agent, TiO 2 and ZrO 2 A glass substrate substantially free of

2. A 2 O 3 The glass substrate of claim 1 , wherein is present in an amount ranging from 5 mol % to 20 mol %.

3. Na in an amount ranging from 0.1 mol % to 6 mol % 2 The glass substrate of claim 1 further comprising O.

4. SnO in an amount ranging from 0 mol% to 2 mol% 2 10. The glass substrate of claim 1 further comprising:

Citation Information

Patent Citations

  • Glass formula used for new touch screen cover plate glass

    CN102690057A

  • Tempered glass substrate and producing method of the same

    JP2010116276A

  • Glass for substrate, and glass substrate

    JP2012106908A

  • A two-step method for strengthening glass

    JP2013536155A

  • Strengthening glass by ion exchange

    US5674790A